Method for producing solid electrolyte
By using heterocyclic compounds as composite agents and mixing them with solid electrolyte raw materials and processing them in a solvent that does not dissolve the electrolyte precursor, the problem of insufficient conductivity when producing solid electrolytes in liquid phase is solved, and solid electrolyte production with high ionic conductivity and chemical stability is achieved.
Patent Information
- Application Number
- JP2021078665
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-27
- Filing Date
- 2021-05-06
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2040-12-21
AI Technical Summary
When the existing liquid phase method produces solid electrolytes, it is difficult to achieve high ionic conductivity similar to that of solid phase method, and the electrolyte components are easily separated and failed during the precipitation process.
A composite agent containing a heterocyclic compound is mixed with a solid electrolyte raw material and treated in a solvent that does not dissolve the electrolyte precursor to form an electrolyte precursor. The composite agent is then removed by heat treatment to obtain a highly conductive solid electrolyte.
The production of solid electrolytes with high ionic conductivity through liquid phase method is achieved, which avoids the separation and failure of electrolyte components during precipitation, and improves the chemical stability and conductivity of the electrolyte.
Smart Images

Figure 0007655773000005 
Figure 0007655773000006 
Figure 0007655773000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a solid electrolyte. [Background technology]
[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras, and mobile phones, the development of batteries to be used as power sources for these devices has become important. Conventionally, electrolytes containing flammable organic solvents have been used in batteries used for such purposes, but by making the battery fully solid-state, flammable organic solvents are not used in the battery, safety devices can be simplified, and manufacturing costs and productivity are excellent, so that batteries in which the electrolyte is replaced with a solid electrolyte layer are being developed.
[0003] The manufacturing methods of the solid electrolyte used in the solid electrolyte layer are roughly divided into a solid-phase method and a liquid-phase method. The liquid-phase method is further divided into a homogeneous method in which the solid electrolyte material is completely dissolved in a solvent, and a heterogeneous method in which the solid electrolyte material is not completely dissolved and goes through a solid-liquid coexistence suspension. For example, as a solid-phase method, a method is known in which raw materials such as lithium sulfide and diphosphorus pentasulfide are subjected to mechanical milling treatment using a device such as a ball mill or a bead mill, and then heated as necessary to produce an amorphous or crystalline solid electrolyte (see, for example, Patent Document 1). According to this method, a solid electrolyte is obtained by applying mechanical stress to raw materials such as lithium sulfide to promote a reaction between solids.
[0004] On the other hand, as a homogeneous liquid phase method, a method in which a solid electrolyte is dissolved in a solvent and reprecipitated is known (see, for example, Patent Document 2), and as a heterogeneous method, a method in which a solid electrolyte raw material such as lithium sulfide is reacted in a solvent containing a polar aprotic solvent is known (see Patent Documents 3 and 4, and Non-Patent Document 1). For example, Patent Document 4 discloses a method for producing a solid electrolyte with a Li4PS4I structure, which includes a step of using dimethoxyethane (DME) and combining it with a Li3PS4 structure to obtain Li3PS4·DME. The ionic conductivity of the obtained solid electrolyte is 5.5×10 -5S / cm (Calcium doped: 3.9 × 10 -4 In recent years, the liquid phase method has been attracting attention as a method that can be easily and mass-produced in addition to its versatility and applicability in order to commercialize all-solid-state batteries. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2017 / 159667 Brochure [Patent Document 2] JP 2014-191899 A [Patent Document 3] International Publication No. 2014 / 192309 Brochure [Patent Document 4] International Publication No. 2018 / 054709 Brochure [Non-patent literature]
[0006] [Non-Patent Document 1] “CHEMISTRY OF MATERIALS”, 2017, No. 29, pp. 1830-1835 Summary of the Invention [Problem to be solved by the invention]
[0007] However, conventional solid-phase methods involving mechanical milling and other processes are centered on solid-phase reactions, and are able to achieve high ionic conductivity because they make it easy to obtain a solid electrolyte with high purity. In contrast, liquid-phase methods dissolve the solid electrolyte, which can cause decomposition or loss of some of the solid electrolyte components during precipitation, making it more difficult to achieve high ionic conductivity than solid-phase synthesis methods. For example, in the homogeneous method, the raw materials and solid electrolyte are completely dissolved once, so that the components can be uniformly dispersed in the liquid. However, in the subsequent precipitation process, precipitation proceeds according to the solubility specific to each component, so it is extremely difficult to maintain the dispersion state of the components while precipitating. As a result, each component separates and precipitates. In addition, in the homogeneous method, the affinity between the solvent and lithium becomes too strong, so the solvent is difficult to remove even when dried after precipitation. For these reasons, the homogeneous method has the problem that the ionic conductivity of the solid electrolyte is significantly reduced. In the heterogeneous solid-liquid coexistence method, a part of the solid electrolyte is dissolved, and separation occurs due to elution of a specific component, making it difficult to obtain a desired solid electrolyte.
[0008] The present invention has been made in view of the above circumstances, and has an object to provide a production method for obtaining a solid electrolyte having high ionic conductivity by using a liquid phase method. [Means for solving the problem]
[0009] As a result of intensive research into solving the above problems, the present inventors have found that the problems can be solved by the following invention.
[0010] 1. A method for producing a solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, comprising mixing a complexing agent and a solid electrolyte raw material, wherein the complexing agent is a heterocyclic compound having a heterocycle containing two or more heteroatoms. 2. The method for producing a solid electrolyte according to 1 above, wherein the heterocycle is a monocyclic heterocycle having 3 to 12 members. 3. The method for producing a solid electrolyte according to 1 or 2 above, wherein the heterocycle has heteroatoms that are not adjacent to each other. 4. The method for producing a solid electrolyte according to any one of 1 to 3 above, wherein the heterocycle is a 6-membered monocyclic heterocycle. 5. The method for producing a solid electrolyte according to any one of 1 to 4 above, wherein the heterocycle has a heteroatom connected through 2 or 3 carbon atoms. 6. The method for producing a solid electrolyte as described in any one of 1 to 5 above, wherein the heteroatom is at least one atom selected from the group consisting of a nitrogen atom, an oxygen atom, a sulfur atom and a phosphorus atom. 7. The method for producing a solid electrolyte according to any one of 1 to 6 above, wherein the heterocycle is a morpholine ring. 8. The method for producing a solid electrolyte according to any one of 1 to 7 above, wherein the complexing agent is N-methylmorpholine. 9. The method for producing a solid electrolyte according to any one of 1 to 6 above, wherein the heterocycle is a piperazine ring. 10. The method for producing a solid electrolyte according to any one of 1 to 6 and 9 above, wherein the complexing agent is N,N'-dimethylpiperazine. 11. The solid electrolyte is 3- 11. A method for producing a solid electrolyte according to any one of 1 to 10 above, which comprises a skeleton. 12. The method for producing a solid electrolyte according to any one of 1 to 11 above, wherein the solid electrolyte contains a thiolicon region II type crystal structure. 13. The method for producing a solid electrolyte according to any one of 1 to 12 above, wherein the solid electrolyte does not have diffraction peaks at 2θ=17.5° and 26.1° in X-ray diffraction measurement using CuKα rays. 14. The method for producing a solid electrolyte according to any one of 1 to 13 above, wherein the solid electrolyte raw material contains lithium sulfide and diphosphorus pentasulfide. 15. The method for producing a solid electrolyte according to any one of 1 to 14 above, wherein the solid electrolyte raw material contains amorphous Li3PS4 or crystalline Li3PS4. 16. A method for producing the solid electrolyte according to any one of 1 to 15 above, comprising obtaining an electrolyte precursor constituted by a complexing agent, a lithium atom, a sulfur atom, a phosphorus atom and a halogen atom. 17. A method for producing a solid electrolyte according to claim 16, comprising mixing the solid electrolyte raw material, the complexing agent, and a solvent that does not dissolve the electrolyte precursor. 18. The method for producing a solid electrolyte according to 17 above, wherein the solvent is at least one solvent selected from the group consisting of aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, aromatic hydrocarbon solvents, ester solvents, nitrile solvents and ether solvents. 19. A method for producing a solid electrolyte according to any one of 16 to 18, comprising heating the electrolyte precursor. Effect of the Invention
[0011] According to the present invention, a solid electrolyte having high ionic conductivity can be provided by using a liquid phase method. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a flow diagram illustrating an example of a preferred embodiment of the manufacturing method of the present embodiment. [Diagram 2] FIG. 2 is a flow diagram illustrating an example of a preferred embodiment of the manufacturing method of the present embodiment. [Diagram 3] 1 is an X-ray diffraction spectrum of the electrolyte precursor obtained in Example 1. [Figure 4] 1 is an X-ray diffraction spectrum of the crystalline solid electrolyte obtained in Example 1. [Diagram 5] 1 is an X-ray diffraction spectrum of the electrolyte precursor obtained in Example 2. [Figure 6] 1 is an X-ray diffraction spectrum of the crystalline solid electrolyte obtained in Example 2. [Figure 7] 1 is an X-ray diffraction spectrum of the electrolyte precursor obtained in Example 3. [Figure 8] 1 is an X-ray diffraction spectrum of the crystalline solid electrolyte obtained in Example 3. [Figure 9] 1 is an X-ray diffraction spectrum of the electrolyte precursor obtained in Reference Example 1. [Figure 10] 1 is an X-ray diffraction spectrum of the crystalline solid electrolyte obtained in Reference Example 1. [Figure 11] 1 is an X-ray diffraction spectrum of the electrolyte precursor obtained in Reference Example 2. [Figure 12]1 is an X-ray diffraction spectrum of the crystalline solid electrolyte obtained in Reference Example 2. [Figure 13] 1 is an X-ray diffraction spectrum of the electrolyte precursor obtained in Reference Example 3. [Figure 14] 1 is an X-ray diffraction spectrum of the crystalline solid electrolyte obtained in Reference Example 3. [Figure 15] 1 is an X-ray diffraction spectrum of the electrolyte precursor obtained in Reference Example 4. [Figure 16] 1 is an X-ray diffraction spectrum of the crystalline solid electrolyte obtained in Reference Example 4. [Figure 17] 1 is an X-ray diffraction spectrum of the electrolyte precursor obtained in Reference Example 5. [Figure 18] 1 is an X-ray diffraction spectrum of the crystalline solid electrolyte obtained in Reference Example 5. [Figure 19] 1 is an X-ray diffraction spectrum of the electrolyte precursor obtained in Reference Example 6. [Figure 20] 1 is an X-ray diffraction spectrum of the crystalline solid electrolyte obtained in Reference Example 6. [Figure 21] 1 is an X-ray diffraction spectrum of the adherent obtained in Comparative Example 1. [Figure 22] 1 is an X-ray diffraction spectrum of the powder obtained in Comparative Example 2. [Diagram 23] 1 is an X-ray diffraction spectrum of the electrolyte precursor obtained in Example 4. [Figure 24] 1 is an X-ray diffraction spectrum of the crystalline solid electrolyte obtained in Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present invention (hereinafter, sometimes referred to as "the present embodiment") will be described. In this specification, the upper and lower limit values of a numerical range expressed by "greater than or equal to", "less than or equal to", and "to" are values that can be arbitrarily combined, and the numerical values in the examples can also be used as the upper and lower limit values.
[0014] [Method for producing solid electrolyte] The method for producing a solid electrolyte according to the present embodiment is a method for producing a solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, and is characterized by comprising mixing a complexing agent and a solid electrolyte raw material. As the complexing agent, the details of which will be described later, the following complexing agents i to iv are preferably used, namely, a heterocyclic compound having a heterocycle containing two or more heteroatoms (hereinafter, sometimes referred to as "complexing agent i"), a compound having an amino group and a nitrile group (hereinafter, sometimes referred to as "complexing agent ii"), a compound having an alkenyl group and an ether group (hereinafter, sometimes referred to as "complexing agent iii"), or a compound having an amino group and a branched structure (hereinafter, sometimes referred to as "complexing agent iv").
[0015] In this specification, the term "solid electrolyte" refers to an electrolyte that maintains a solid state under a nitrogen atmosphere at 25° C. The solid electrolyte in this embodiment is a solid electrolyte that contains lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms and has ionic conductivity due to the lithium atoms.
[0016] The term "solid electrolyte" includes both crystalline solid electrolytes having a crystal structure and amorphous solid electrolytes. In this specification, the term "crystalline solid electrolyte" refers to a solid electrolyte in which a peak derived from a solid electrolyte is observed in an X-ray diffraction pattern in an X-ray diffraction measurement, and it does not matter whether or not there is a peak derived from the raw material of the solid electrolyte. That is, the crystalline solid electrolyte includes a crystal structure derived from a solid electrolyte, and a part of the crystal structure may be derived from the solid electrolyte, or the whole of the crystal structure may be derived from the solid electrolyte. And, as long as the crystalline solid electrolyte has the above-mentioned X-ray diffraction pattern, a part of the crystalline solid electrolyte may include an amorphous solid electrolyte. Therefore, the crystalline solid electrolyte includes so-called glass ceramics obtained by heating an amorphous solid electrolyte to a crystallization temperature or higher. In this specification, the term "amorphous solid electrolyte" refers to an electrolyte that has an X-ray diffraction pattern that is a halo pattern in which no peaks other than those derived from the material are observed in an X-ray diffraction measurement, and does not matter whether or not there are peaks derived from the raw materials of the solid electrolyte.
[0017] The solid electrolyte raw material used in the method for producing a solid electrolyte of the present embodiment preferably contains lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, from the viewpoint of obtaining a solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, and examples of such a solid electrolyte include a solid electrolyte having a Li3PS4 structure. Therefore, the method for producing a solid electrolyte of this embodiment preferably includes the following four embodiments depending on whether or not a solid electrolyte having a Li3PS4 structure or the like is used as a solid electrolyte raw material, and whether or not a solvent is used. Examples of preferred forms of these four embodiments are shown in Figures 1 (embodiments A and B) and 2 (embodiments C and D). That is, the method for producing a solid electrolyte of this embodiment preferably includes (embodiment A) a production method using raw materials such as lithium sulfide and diphosphorus pentasulfide as a solid electrolyte raw material and the above-mentioned specific complexing agent; (embodiment B) a production method using the above-mentioned specific complexing agent as a solid electrolyte raw material containing the Li3PS4 structure or the like as a raw material, which is the electrolyte main structure; (embodiment C) a production method in which a solvent is added to raw materials such as lithium sulfide as a solid electrolyte raw material and the above-mentioned specific complexing agent in the above-mentioned embodiment A; (embodiment D) a production method in which a solvent is added to raw materials such as Li3PS4 structure as a solid electrolyte raw material and the above-mentioned specific complexing agent in the above-mentioned embodiment B;
[0018] Hereinafter, embodiments A to D will be described in this order.
[0019] As shown in FIG. 1, embodiment A is a form in which lithium sulfide and diphosphorus pentasulfide are used as the solid electrolyte raw material in the manufacturing method of this embodiment, which is characterized by comprising mixing a solid electrolyte raw material and a complexing agent, preferably a heterocyclic compound having a heterocycle containing two or more heteroatoms (complexing agent i), a compound having an amino group and a nitrile group (complexing agent ii), a compound having an alkenyl group and an ether group (complexing agent iii), or a compound having an amino group and a branched structure (complexing agent iv), etc. A solid electrolyte raw material is obtained by mixing the solid electrolyte raw material and the specific complexing agent, and an electrolyte precursor-containing material, which is usually a suspension, is obtained by drying the electrolyte precursor. Furthermore, an amorphous or crystalline solid electrolyte is obtained by heating the electrolyte precursor. The following description will be given starting with embodiment A, but the phrase "of this embodiment" is also applicable to other embodiments.
[0020] (Solid electrolyte raw material) The solid electrolyte raw material used in this embodiment preferably contains lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, from the viewpoint of obtaining a solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms. As the solid electrolyte raw material, for example, a compound containing at least one of lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms can be used alone or in combination. More specifically, lithium sulfide; lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide; phosphorus sulfides such as diphosphorus trisulfide (P2S3) and diphosphorus pentasulfide (P2S5); various phosphorus fluorides (PF3, PF5), various phosphorus chlorides (PCl3, PCl5, P2Cl4), various phosphorus bromides (PBr3, PBr5), various phosphorus iodides (PI3, P2I4), and the like can be used. Representative examples of the starting material include phosphorus halides such as thiophosphoryl fluoride (PSF3), thiophosphoryl chloride (PSCl3), thiophosphoryl bromide (PSBr3), thiophosphoryl iodide (PSI3), thiophosphoryl fluoride dichloride (PSCl2F), and thiophosphoryl fluoride dibromide (PSBr2F); and raw materials consisting of at least two atoms selected from the above four types of atoms, such as simple halogens such as fluorine (F2), chlorine (Cl2), bromine (Br2), and iodine (I2), preferably bromine (Br2) and iodine (I2).
[0021] Examples of the raw materials that can be used other than the above include raw materials that contain at least one atom selected from the above four types of atoms and also contain atoms other than the four types of atoms, more specifically, lithium compounds such as lithium oxide, lithium hydroxide, and lithium carbonate; alkali metal sulfides such as sodium sulfide, potassium sulfide, rubidium sulfide, and cesium sulfide; metal sulfides such as silicon sulfide, germanium sulfide, boron sulfide, gallium sulfide, tin sulfide (SnS, SnS2), aluminum sulfide, and zinc sulfide; phosphate compounds such as sodium phosphate and lithium phosphate; halides of alkali metals other than lithium, such as sodium iodide, sodium fluoride, sodium chloride, and sodium bromide, and the like; metal halides such as aluminum halides, silicon halides, germanium halides, arsenic halides, selenium halides, tin halides, antimony halides, tellurium halides, and bismuth halides; and phosphorus oxyhalides such as phosphorus oxychloride (POCl3) and phosphorus oxybromide (POBr3).
[0022] In this embodiment, from the viewpoint of more easily obtaining a solid electrolyte having high ionic conductivity, the raw materials are preferably lithium sulfide, phosphorus sulfide such as diphosphorus trisulfide (P2S3) and diphosphorus pentasulfide (P2S5), halogen elements such as fluorine (F2), chlorine (Cl2), bromine (Br2), and iodine (I2), and lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide. Preferred combinations of raw materials include, for example, a combination of lithium sulfide, diphosphorus pentasulfide, and lithium halides, and a combination of lithium sulfide, diphosphorus pentasulfide, and halogen elements, and lithium bromide and lithium iodide are preferred as lithium halides, and bromine and iodine are preferred as halogen elements.
[0023] The lithium sulfide used in this embodiment is preferably in the form of particles. The average particle size of lithium sulfide particles (D 50 In this specification, the average particle size (D 50 ) is the particle size at which the particle size distribution cumulative curve is accumulated from the smallest particle size to 50% of the total, and the volume distribution is the average particle size that can be measured, for example, using a laser diffraction / scattering particle size distribution measuring device. Among the above-mentioned examples of raw materials, the solid raw materials preferably have an average particle size similar to that of the lithium sulfide particles, that is, within the same range as the average particle size of the lithium sulfide particles.
[0024] When lithium sulfide, diphosphorus pentasulfide, and lithium halide are used as raw materials, the ratio of lithium sulfide to the total of lithium sulfide and diphosphorus pentasulfide is preferably 70 to 80 mol%, more preferably 72 to 78 mol%, and even more preferably 74 to 76 mol%, from the viewpoint of obtaining higher chemical stability and higher ionic conductivity. When lithium sulfide, diphosphorus pentasulfide, lithium halide, and other raw materials used as necessary are used, the content of lithium sulfide and diphosphorus pentasulfide relative to the total of these is preferably 60 to 100 mol%, more preferably 65 to 90 mol%, and even more preferably 70 to 80 mol%. Furthermore, when lithium bromide and lithium iodide are used in combination as the lithium halide, from the viewpoint of improving ion conductivity, the ratio of lithium bromide to the total of lithium bromide and lithium iodide is preferably 1 to 99 mol%, more preferably 20 to 90 mol%, even more preferably 40 to 80 mol%, and particularly preferably 50 to 70 mol%.
[0025] In the case where a halogen element is used as a raw material, and lithium sulfide and diphosphorus pentasulfide are used, the ratio of the number of moles of lithium sulfide excluding the same number of moles of lithium sulfide as the halogen element to the total number of moles of lithium sulfide and diphosphorus pentasulfide excluding the same number of moles of lithium sulfide as the halogen element is preferably within the range of 60 to 90%, more preferably within the range of 65 to 85%, even more preferably within the range of 68 to 82%, even more preferably within the range of 72 to 78%, and particularly preferably within the range of 73 to 77%. This is because higher ion conductivity can be obtained at these ratios. From the same viewpoint, when lithium sulfide, diphosphorus pentasulfide, and a halogen element are used, the content of the halogen element relative to the total amount of lithium sulfide, diphosphorus pentasulfide, and a halogen element is preferably 1 to 50 mol%, more preferably 2 to 40 mol%, even more preferably 3 to 25 mol%, and even more preferably 3 to 15 mol%.
[0026] When lithium sulfide, diphosphorus pentasulfide, a halogen element, and a lithium halide are used, the content of the halogen element (α mol %) and the content of the lithium halide (β mol %) relative to the total amount thereof preferably satisfy the following formula (2), more preferably satisfy the following formula (3), even more preferably satisfy the following formula (4), and even more preferably satisfy the following formula (5). 2≦2α+β≦100…(2) 4≦2α+β≦80 …(3) 6≦2α+β≦50 …(4) 6≦2α+β≦30 …(5)
[0027] When two types of halogens are used as simple substances, the molar number of one halogen atom in the substance is A1 and the molar number of the other halogen atom in the substance is A2, and A1:A2 is preferably 1 to 99:99 to 1, more preferably 10:90 to 90:10, even more preferably 20:80 to 80:20, and even more preferably 30:70 to 70:30.
[0028] Furthermore, when the two types of halogen elements are bromine and iodine, the molar number of bromine is B1 and the molar number of iodine is B2, then B1:B2 is preferably 1 to 99:99 to 1, more preferably 15:85 to 90:10, even more preferably 20:80 to 80:20, even more preferably 30:70 to 75:25, and particularly preferably 35:65 to 75:25.
[0029] (Complexing Agent) In the method for producing the solid electrolyte of this embodiment, it is necessary to use a complexing agent, and preferably, a specific complexing agent such as a heterocyclic compound having a heterocycle containing two or more heteroatoms (complexing agent i), a compound having an amino group and a nitrile group (complexing agent ii), a compound having an alkenyl group and an ether group (complexing agent iii), or a compound having an amino group and a branched structure (complexing agent iv) is used.
[0030] In this specification, the complexing agent means a substance capable of forming a complex with lithium atoms, and has a property of promoting the formation of an electrolyte precursor by acting with sulfides, halides, etc. containing lithium atoms contained in the raw material. The reason why the complexing agent contributes to the formation of the crystal structure of the solid electrolyte is not clear, but the following is presumed. Since heteroatoms have a high affinity with lithium atoms, it is believed that the complexing agent having a heteroatom easily builds a correlation with lithium atoms, and the complexing agent easily forms a complex with lithium atoms and acts with sulfides, halides, etc. containing lithium atoms, which makes it easier to promote the formation of an electrolyte precursor.
[0031] The complexing agent can be used without any particular limitation as long as it has the above-mentioned properties, and preferably, specific complexing agents such as the above-mentioned complexing agents i to iv are used. These specific complexing agents have functional groups and structures containing heteroatoms such as nitrogen atoms and oxygen atoms in their molecules, and therefore have the property of easily coordinating (bonding) with lithium atoms as described above. Therefore, these specific complexing agents have improved affinity with lithium atoms, and are more likely to form complexes with lithium atoms. The complexing agent has a high affinity with lithium atoms due to the functional group and structure containing heteroatoms such as nitrogen and oxygen atoms in its molecule, and is considered to have a property of easily forming an aggregate by combining with a lithium-containing structure such as Li3PS4 containing a PS4 structure, which is present as a main structure in the solid electrolyte obtained by the manufacturing method of this embodiment, and a lithium-containing raw material such as lithium halide. Therefore, by mixing the solid electrolyte raw material with the complexing agent having the specific structure, a lithium-containing structure such as PS4 structure or an aggregate via the complexing agent, a lithium-containing raw material such as lithium halide or an aggregate via the complexing agent are evenly present, and an electrolyte precursor in which halogen atoms are more dispersed and fixed is obtained, and as a result, a solid electrolyte having high ion conductivity and suppressed generation of hydrogen sulfide is obtained. Below, the specific complexing agents i to iv preferably used in this embodiment will be described in order.
[0032] (Complexing Agent I) The complexing agent I is a heterocyclic compound having a heterocycle containing two or more heteroatoms. Since the complexing agent I has heteroatoms, as described above, it is easy to obtain an electrolyte precursor, and a solid electrolyte having high ionic conductivity and suppressed generation of hydrogen sulfide can be obtained. In addition, since the complexing agent i further has a heterocyclic structure, the reaction in which at least two heteroatoms in the heterocyclic ring form a complex with a lithium atom and the decomposition of the complex occurs in a well-balanced manner due to the steric hindrance caused by the heterocyclic structure, so that structures containing lithium such as PS4 structures or aggregates via a complexing agent, raw materials containing lithium such as lithium halides or aggregates via a complexing agent are evenly present, and the solid electrolyte precursor is easily formed, and as a result, the solid electrolyte obtained by the manufacturing method of this embodiment is considered to be a solid electrolyte that can improve ion conductivity. The above-mentioned matters are sometimes referred to as the "effect of using the complexing agent i".
[0033] From the viewpoint of easily obtaining the effect of using the complexing agent i, examples of the heteroatom that the complexing agent i has include an oxygen atom, a nitrogen atom, a chlorine atom, a phosphorus atom, a sulfur atom, etc., and an oxygen atom, a nitrogen atom, a chlorine atom, and a phosphorus atom are preferred, and an oxygen atom and a nitrogen atom are more preferred. In addition, two or more heteroatoms may be the same or different, and it is preferred to have different heteroatoms, and in particular, a combination of an oxygen atom and a nitrogen atom is preferred. In addition, the number of heteroatoms contained in the complexing agent i is usually 2 or more, and preferably 6 or less, more preferably 4 or less, and further preferably 3 or less, from the viewpoint of easily obtaining the effect of using the complexing agent i. From the above viewpoint, the number of heteroatoms is most preferably 2.
[0034] Considering the ease of obtaining the effect of using the complexing agent i, it is preferable that the heterocycle has heteroatoms that are not adjacent to each other. That is, it is preferable that at least two of the two or more heteroatoms are connected by carbon atoms. For example, the ring in which the heterocycle is a four-membered ring and has two heteroatoms, and the two heteroatoms are connected via a carbon atom, can be exemplified by ring a having one heteroatom, a carbon atom, another heteroatom, and a carbon atom in this order, or ring b having one heteroatom, a carbon atom, a carbon atom, and another heteroatom in this order, but it is preferable that both of the two heteroatoms are rings having carbon atoms on both sides, as in ring a. Furthermore, when at least two heteroatoms are connected by a carbon atom, the number of carbon atoms cannot be determined in general depending on the number of atoms forming the heterocycle, but taking into consideration the ease of obtaining the effect of using the complexing agent i, the number is preferably 1 or more, more preferably 2 or more, and the upper limit is preferably 5 or less, more preferably 4 or less, even more preferably 3 or less, and particularly preferably 2 or 3.
[0035] The heterocycle of the complexing agent i may be any one of a monocyclic heterocycle, a bicyclic heterocycle, a tricyclic heterocycle, and a polycyclic heterocycle having four or more rings. In consideration of the ease of obtaining the effect of using the complexing agent i and the ease of availability, the complexing agent i is preferably a monocyclic heterocycle. From the same viewpoints as above, the heterocycle is preferably 3-membered or more, more preferably 4-membered or more, and even more preferably 5-membered or more, and the upper limit is preferably 12-membered or less, more preferably 10-membered or less, and even more preferably 8-membered or less. Also, the heterocycle is particularly preferably 6-membered.
[0036] Examples of monocyclic heterocycles having two or more heteroatoms that can be preferably used in the present embodiment include, from the same viewpoints as above, three-membered rings containing a nitrogen atom, such as a diaziridine ring, a diazirine ring, or a diazylene ring; three-membered rings containing a nitrogen atom / oxygen atom, such as an oxazolidine ring or an oxazoline ring; three-membered rings containing an oxygen atom, such as a dioxirane ring; four-membered rings containing a nitrogen atom, such as a diazetidine ring, a diazeto ring, a triazetidine ring, or a triazeto ring; four-membered rings containing an oxygen atom, such as a dioxetane ring or a dioxete ring; a dithietane ring, ... 4-membered rings such as sulfur atom-containing 4-membered rings such as an ethoxy ring; nitrogen atom-containing 5-membered rings such as a pyrazolidine ring, a pyrazoline ring, a pyrazole ring, an imidazolidine ring, an imidazoline ring, an imidazole ring, a triazolidine ring, a triazoline ring, a triazole ring, a tetrazolidine ring, a tetrizoline ring, a tetrazole ring, a pentazole ring; nitrogen atom-containing 5-membered rings such as an oxazolidine ring, an oxazoline ring, a furazan ring, an oxadiazole ring; nitrogen atom-containing 5-membered rings such as a thiazolidine ring, a thiazoline ring, a thiadiazole ring, a dithiazole ring, etc. / 5-membered rings containing a sulfur atom, 5-membered rings containing an oxygen atom such as a dioxolane ring, 5-membered rings containing a sulfur atom such as a dithiolane ring; 6-membered rings containing a nitrogen atom such as a piperazine ring, a pyridazine ring, a pyrimidine ring, a pyrazine ring, a triazinane ring, a triazine ring, a tetrazinane ring, a tetrazine ring, a pentazinane ring, a pentazine ring; 6-membered rings containing a nitrogen atom such as a morpholine ring or an oxazine ring; 6-membered rings containing a nitrogen atom such as a thiomorpholine ring or a thiazine ring; 6-membered rings containing a sulfur atom such as a dioxane ring or a dioxine ring; Main examples of such rings include 6-membered rings, sulfur-containing 6-membered rings such as a dithiane ring and a dithiin ring; 7-membered rings containing a nitrogen atom such as a diazepane ring and a diazepine ring, 7-membered rings containing a nitrogen atom / sulfur atom such as a thiazepine ring, and 7-membered rings containing a sulfur atom such as a dithiepane ring and a trithiepane ring; 8-membered rings containing a nitrogen atom such as a diazocane ring, 8-membered rings containing an oxygen atom such as a dioxocane ring and a trioxocane ring, and 8-membered rings containing a sulfur atom such as a dithiocane ring and a trithiocane ring; and 9-membered rings containing a nitrogen atom such as a diazonane ring and a diazonine ring. Although heterocycles having commonly used names are mainly exemplified, the heterocycles that can be used in the present embodiment are not limited to these exemplified heterocycles. For example, the triazolidine ring also includes isomers such as a 1,2,3-triazolidine ring and a 1,2,4-triazolidine ring.
[0037] Among the above heterocycles, as mentioned above, 6-membered rings are particularly preferred, 6-membered rings containing nitrogen and oxygen atoms (nitrogen atom / oxygen atom-containing 6-membered rings) are preferred, and morpholine rings are preferred. The "morpholine" of the morpholine ring is usually also called tetrahydro-1,4-oxazine, but there are isomers such as tetrahydro-1,2-oxazine and tetrahydro-1,3-oxazine. The morpholine ring in the complexing agent i may be any, but it is preferably tetrahydro-1,4-oxazine, which is usually called morpholine.
[0038] The complexing agent i may be a heterocyclic compound having the above-mentioned heterocycle, and may be a heterocyclic compound which is the above-mentioned heterocycle itself, or a heterocyclic compound which has an aliphatic hydrocarbon group such as an alkyl group or an alkenyl group, the above-mentioned heteroatom, or a heteroatom-containing group containing the above-mentioned heteroatom such as a hydroxyl group added to the above-mentioned heterocycle, and among them, a heterocyclic compound to which an aliphatic hydrocarbon group is added is preferred, and a heterocyclic compound to which an alkyl group is added is more preferred.These groups may be added to the carbon atom or the heteroatom in the heterocyclic compound, but from the viewpoint of easily obtaining the effect of using the complexing agent i, it is preferred that they are added to the heteroatom. The number of carbon atoms in the aliphatic hydrocarbon group is preferably 1 or more, with the upper limit being preferably 12 or less, more preferably 8 or less, even more preferably 4 or less, and still more preferably 2 or less. In addition, the hydrocarbon group may be linear or branched.
[0039] Particularly preferred compounds of the complexing agent i, from the viewpoint of easily obtaining the effect of using the complexing agent i, are amine compounds also called "heterocyclic amines" such as morpholine ring, piperazine ring and piperidine ring themselves, i.e., morpholine, piperazine and piperidine, as well as compounds having an aliphatic hydrocarbon group added to these rings (these compounds are also called "morpholine compounds", "piperazine compounds" and "piperidine compounds", respectively), among which morpholine, morpholine compounds having an aliphatic hydrocarbon group added to morpholine, piperazine, and piperazine having an aliphatic hydrocarbon group are particularly preferred. Preferred are piperazine compounds having an alkyl group added to morpholine, and more preferred are morpholine compounds having an alkyl group added to a nitrogen atom of the morpholine ring, and piperazine compounds having an alkyl group added to a nitrogen atom of the piperazine ring, and still more preferred are morpholine compounds having an alkyl group added to a nitrogen atom of the morpholine ring, and piperazine compounds having an alkyl group added to a nitrogen atom of the piperazine ring, and most preferred are piperazine compounds having alkyl groups added to all nitrogen atoms of the piperazine ring, such as N-methylmorpholine (especially N-methyl-tetrahydro-1,4-oxazine) and N,N'-dimethylpiperazine. The above complexing agents i may be used alone or in combination of two or more.
[0040] (Complexing Agent II) The complexing agent II is a complexing agent having an amino group and a nitrile group. Since the complexing agent II has a nitrogen atom as a heteroatom, as described above, it is easy to obtain an electrolyte precursor, and a solid electrolyte having high ionic conductivity can be obtained. In addition, by having different types of functional groups containing heteroatoms, the reaction in which the two heteroatoms and the lithium atom form a complex, and the decomposition of the complex occurs in a well-balanced manner by using the different functional groups appropriately, so that the solid electrolyte obtained by the manufacturing method of this embodiment is considered to be a solid electrolyte that can improve ion conductivity, similar to the above complexing agent. The above-mentioned matters are sometimes referred to as "the effect of using complexing agent II".
[0041] There are no particular limitations on the structure of the complexing agent II as long as it has an amino group and a nitrile group. However, in consideration of the ease with which the effect of using the complexing agent II can be obtained, it is preferable that the complexing agent II be an acyclic compound that does not have a cyclic structure such as a cyclo ring, an aromatic ring, or a heterocyclic ring in the molecule, and among these, an acyclic aliphatic compound is preferable.
[0042] The amino group of the complexing agent II may be any of a primary amino group, a secondary amino group, and a tertiary amino group. In consideration of the ease of obtaining the effect of using the complexing agent II, a secondary amino group or a tertiary amino group is preferable, and a tertiary amino group is more preferable.
[0043] The amino group that the complexing agent ii can have is, for example, one represented by the following general formula (1).
[0044] [ka] (In general formula (1), R 11 and R 12 each independently represents a hydrogen atom or an organic group.
[0045] R 11 and R 12 Examples of the organic group of R include an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, and a heterocyclic group. Taking into consideration the ease of obtaining the effect of using the complexing agent ii and the ease of availability, an aliphatic hydrocarbon group is preferred. 11 and R 12 When R is an organic group, 11 and R 12 may be the same or different, and is preferably the same in consideration of availability and the like.
[0046] Examples of the aliphatic hydrocarbon group include alkyl groups and alkenyl groups. Taking into consideration the ease with which the effect of using the above complexing agent ii can be obtained and ease of availability, alkyl groups are preferred. From the same viewpoint, the number of carbon atoms in the aliphatic hydrocarbon group, in the case of an alkyl group, is preferably 1 or more, with the upper limit being preferably 12 or less, more preferably 8 or less, even more preferably 4 or less, and still more preferably 2 or less. In the case of an alkenyl group, the number of carbon atoms is preferably 2 or more, with the upper limit being preferably 12 or less, more preferably 8 or less, even more preferably 4 or less, and particularly preferably 2. In addition, the aliphatic hydrocarbon group may be either linear or branched, but is preferably linear.
[0047] As described above, the amino group is preferably a secondary amino group or a tertiary amino group, and more preferably a tertiary amino group. 11 and R 12 At least one of R is preferably an organic group. 11 and R 12 It is more preferable that each of the groups is an organic group.
[0048] The complexing agent ii is preferably a compound represented by the general formula (2).
[0049] [ka] (In general formula (2), R 21 and R 22 each independently represents a hydrogen atom or an organic group; X 21 represents a single bond or an organic group.
[0050] R 21 and R 22 The organic group of R 11 and R 12 The preferred embodiment is the same as R 11 and R 12 is the same as: X 21 Examples of the organic group of X include an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, and a heterocyclic group. Taking into consideration the ease of obtaining the effect of using the complexing agent ii and the ease of availability, an aliphatic hydrocarbon group is preferred. 21The aliphatic hydrocarbon group of is preferably an alkylene group or an alkenylene group, and is preferably an alkylene group. The number of carbon atoms of the aliphatic hydrocarbon group is preferably 1 or more in the case of an alkylene group, and the upper limit is preferably 12 or less, more preferably 8 or less, even more preferably 4 or less, and even more preferably 2 or less. X 21 Particularly preferred organic groups are a methylene group (methyl-1,1-diyl group) and an ethylene group (ethyl-1,2-diyl group).
[0051] The aliphatic hydrocarbon group may be either linear or branched. Taking into consideration the ease of obtaining the effect of using the above-mentioned complexing agent II and ease of availability, the linear group is preferable. Furthermore, it is preferable that the complexing agent II does not have a branched organic group, i.e., it is a compound that does not have a branched structure.
[0052] Particularly preferred examples of the complexing agent ii include those represented by the general formula (2) above, 21 and R 22 is a methyl group, and X 21 is a methylene group (methyl-1,1-diyl group), N,N-dimethylaminoacetonitrile, R 21 and R 22 is an ethyl group, and X 21 is a methylene group (methyl-1,1-diyl group), N,N-diethylaminoacetonitrile, R 21 and R 22 is a methyl group, and X 21 is an ethylene group (ethyl-1,2-diyl group). The above complexing agents ii may be used alone or in combination of two or more.
[0053] (Complexing Agent III) The complexing agent III is a complexing agent having an alkenyl group and an ether group. Since the complexing agent III has a heteroatom, as described above, it is easy to obtain an electrolyte precursor, and a solid electrolyte having high ionic conductivity can be obtained. In addition, by having an alkenyl group, which is an unsaturated group, the reaction of forming a complex with the ether group and the decomposition of the complex occur in a well-balanced manner. As a result, it is considered that the solid electrolyte obtained by the production method of the present embodiment is a solid electrolyte in which ionic conductivity can be improved, similarly to the above-mentioned complexing agent. The above phenomenon may be referred to as the "effect of using complexing agent iii."
[0054] The complexing agent III is not particularly limited in structure other than that as long as it has an alkenyl group and an ether group; however, by simultaneously having an alkenyl group and an ether group, the above-mentioned effect of using the complexing agent III can be obtained, and in consideration of the ease of obtaining the effect, the complexing agent III is preferably an acyclic compound not having a cyclic structure such as a cyclo ring, an aromatic ring, or a heterocycle in the molecule, and among these, an acyclic aliphatic compound is preferable.
[0055] Considering the ease of obtaining the effect of using the complexing agent III, the number of carbon atoms in the alkenyl group of the complexing agent III is preferably 2 or more, more preferably 3 or more, and the upper limit is preferably 12 or less, more preferably 8 or less, even more preferably 4 or less, and particularly preferably 3. From the same viewpoint, the number of alkenyl groups in the complexing agent iii is preferably 2 or more, and the upper limit is preferably 4 or less, more preferably 3 or less, and particularly preferably 2. When the complexing agent iii has multiple alkenyl groups, the multiple alkenyl groups may be the same or different, and in consideration of ease of availability, etc., it is preferable that the alkenyl groups are the same.
[0056] The complexing agent iii is preferably a compound represented by the general formula (3).
[0057] [ka] (In general formula (3), R 31 and R 32 each independently represents a hydrogen atom, an alkenyl group, or an organic group; R 31 and R32 At least one of the groups represents an alkenyl group.
[0058] R 31 and R 32 The alkenyl group is as described above, and at least one of them is an alkenyl group. The alkenyl group may be either linear or branched, and in consideration of the ease of obtaining the effect of using the complexing agent iii, the linear one is preferred.
[0059] R 31 and R 32 Examples of the organic group include an alkyl group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, and a heterocyclic group. In consideration of the ease of obtaining the effect of using the complexing agent iii and the ease of availability, an alkyl group is preferred.
[0060] Considering the ease with which the effect of using the complexing agent iii can be obtained, the complexing agent iii preferably has an unsaturated bond at its terminal, and more preferably has unsaturated bonds at both terminals.
[0061] Particularly preferred examples of the complexing agent iii include ethyl propenyl ether, isopropenyl methyl ether, diallyl ether, butenyl propenyl ether, methyl butenyl ether, ethyl butenyl ether, dibutenyl ether, and the like. Diallyl ether is preferred, and diallyl ether (4-oxa-1,6-heptadiene) having unsaturated groups at both ends is particularly preferred. The complexing agent iii may be used alone or in combination of two or more kinds.
[0062] (Complexing Agent IV) The complexing agent IV is a complexing agent having an amino group and a branched structure. Since the complexing agent IV has a nitrogen atom as a heteroatom, as described above, it is easy to obtain an electrolyte precursor, and a solid electrolyte having high ionic conductivity can be obtained. In addition, since the solid electrolyte has a branched structure, the reaction in which the amino group having a nitrogen atom and the lithium atom form a complex and the decomposition of the complex due to steric hindrance occur in a well-balanced manner. As a result, it is considered that the solid electrolyte obtained by the production method of the present embodiment is a solid electrolyte in which ionic conductivity can be improved, similar to the above-mentioned complexing agent. The above phenomenon is sometimes referred to as "the effect of using complexing agent IV."
[0063] The complexing agent iv is not particularly limited in terms of other structure as long as it has an amino group and a branched structure. However, in consideration of the ease of obtaining the effect of using the complexing agent iv, it is preferable that the complexing agent iv be an acyclic compound that does not have a cyclic structure such as a cyclo ring, aromatic ring, or heterocycle in the molecule, and among these, an acyclic aliphatic compound is preferable.
[0064] The amino group of the complexing agent iv may be any of a primary amino group, a secondary amino group, and a tertiary amino group. Considering the ease of obtaining the effect of using the complexing agent iv, a secondary amino group or a tertiary amino group is preferable, and in particular, considering the overall balance of the decomposition of the complex due to the steric hindrance of the branched structure, a secondary amino group is more preferable.
[0065] In consideration of providing a suitable degree of steric hindrance to facilitate the effect of using the complexing agent iv, the complexing agent iv preferably has one or more branched structures in the molecule, more preferably two or more, and the upper limit is preferably 8 or less, more preferably 4 or less, even more preferably 3 or less, and particularly preferably 2. From the same viewpoint, the complexing agent iv preferably has a branched structure at its terminal, and more preferably has a branched structure at both terminals.
[0066] The complexing agent iv is preferably a compound represented by the general formula (4).
[0067] [ka] (In general formula (4), R 41 , R42 and R 43 each independently represents a hydrogen atom or an organic group; R 41 , R 42 and R 43 At least one of represents an organic group.
[0068] R 41 , R 42 and R 43 Examples of the organic group of R include an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, and a heterocyclic group. Taking into consideration the ease of obtaining the effect of using the complexing agent iv and the ease of availability, an aliphatic hydrocarbon group is preferred. 41 , R 42 and R 43 When two or more of R are organic groups, two or more R 41 , R 42 and R 43 The organic groups may be the same or different, but are preferably the same in consideration of availability and the like. As described above, the complexing agent iv is preferably a secondary amino group or a tertiary amino group, and more preferably a secondary amino group. 41 , R 42 and R 43 It is preferable that at least one of them is an organic group, and it is more preferable that two of them are organic groups.
[0069] Examples of the aliphatic hydrocarbon group include an alkyl group and an alkenyl group, and considering the ease of obtaining the effect of using the complexing agent iv and the ease of availability, an alkyl group is preferred. Considering the ease of obtaining the effect of using the complexing agent iv and the ease of availability, the carbon number of the aliphatic hydrocarbon group is preferably 1 or more, more preferably 2 or more, and even more preferably 3 or more, and the upper limit is preferably 12 or less, more preferably 8 or less, even more preferably 6 or less, and even more preferably 4 or less, in the case of an alkyl group. From the same viewpoint, the carbon number of the alkenyl group is preferably 2 or more, more preferably 3 or more, and the upper limit is preferably 12 or less, more preferably 8 or less, and even more preferably 4 or less. In the present embodiment, particularly preferred specific examples of the alkyl group include an isopropyl group (1-methylethyl group), a sec-butyl group (1-methylpropyl group), a tert-butyl group (1,1-dimethylethyl group), and an isobutyl group (2-methylpropyl group). Of these, an isopropyl group (1-methylethyl group) and a tert-butyl group (1,1-dimethylethyl group) are preferred.
[0070] The aliphatic hydrocarbon group may be either linear or branched. In consideration of the ease of obtaining the effect of using the above complexing agent iv, R 41 , R 42 and R 43 It is preferred that at least one of them is branched, and it is more preferred that two of them are branched. From the same viewpoint, the complexing agent iv preferably has a branched structure at its terminal, and more preferably has branched structures at both terminals. When the complexing agent iv has branched structures at both terminals, the branched structures may be the same or different, but considering the ease of obtaining the effect of using the complexing agent iv and the ease of availability, it is preferable that the branched structures are the same.
[0071] The complexing agent iv is, for example, R 41 , R 42 and R 43 When iv has an alkyl group exemplified as a specific example of the particularly preferred alkyl group, that is, an isopropyl group (1-methylethyl group), a sec-butyl group (1-methylpropyl group), a tert-butyl group (1,1-dimethylethyl group), or an isobutyl group (2-methylpropyl group), the terminal of the complexing agent iv will have an isopropyl group (1-methylethyl group), a sec-butyl group (1-methylpropyl group), a tert-butyl group (1,1-dimethylethyl group), or an isopropyl group (1-methylethyl group), respectively.
[0072] As the complexing agent iv, particularly preferred compounds include compounds having an amino group and an isopropyl group or a tert-butyl group at the terminal, more preferred compounds are compounds having an amino group and an isopropyl group or a tert-butyl group at both terminals, and even more preferred compounds in which the isopropyl group or the tert-butyl group at both terminals is connected to a nitrogen atom, i.e., R 41 , R 42 and R 43 Examples of the diisopropylamine and diisobutylamine include diisopropylamine and diisobutylamine, in which two of the groups are isopropyl groups or tert-butyl groups and the remaining one is a hydrogen atom. The above complexing agents iv may be used alone or in combination of two or more.
[0073] (Other complexing agents) Examples of complexing agents other than the above-mentioned complexing agents include compounds having a group containing a heteroatom, such as an oxygen atom, a nitrogen atom, or a halogen atom (e.g., a chlorine atom), which have a high affinity with lithium atoms and are therefore included as complexing agents other than the above-mentioned complexing agents.
[0074] Examples of the other complexing agent include alcohol-based solvents such as ethanol and butanol; ester-based solvents such as ethyl acetate and butyl acetate; aldehyde-based solvents such as formaldehyde, acetaldehyde, and dimethylformamide; ketone-based solvents such as acetone and methyl ethyl ketone; ether-based solvents such as diethyl ether, diisopropyl ether, dibutyl ether, tetrahydrofuran, dimethoxyethane, cyclopentyl methyl ether, tert-butyl methyl ether, and anisole; halogen-containing aromatic hydrocarbon solvents such as trifluoromethylbenzene, nitrobenzene, chlorobenzene, chlorotoluene, and bromobenzene; amine-based solvents such as tetramethylethylenediamine, tetraethylethylenediamine, tetramethyldiaminopropane, tetraethyldiaminopropane, cyclopropanediamine, tolylenediamine, and tetraethylenepentamine; and solvents containing carbon atoms and heteroatoms such as acetonitrile, dimethylsulfoxide, and carbon disulfide. Among these, ether-based solvents are preferred, with diethyl ether, diisopropyl ether, dibutyl ether, and tetrahydrofuran being more preferred, and diethyl ether, diisopropyl ether, and dibutyl ether being even more preferred. The above other complexing agents may be used alone or in combination of two or more.
[0075] (mixture) As shown in the flow diagram of Fig. 1, a solid electrolyte raw material and a complexing agent, preferably the above-mentioned specific complexing agent, are mixed. In this embodiment, the solid electrolyte raw material and the complexing agent may be mixed in either a solid or liquid form, but since the solid electrolyte raw material usually contains a solid and the complexing agent is liquid, they are usually mixed in a form in which the solid solid electrolyte raw material exists in the liquid complexing agent.
[0076] The amount of the solid electrolyte raw material is preferably 5 g or more, more preferably 10 g or more, even more preferably 30 g or more, and even more preferably 50 g or more, with the upper limit being preferably 500 g or less, more preferably 400 g or less, even more preferably 300 g or less, and even more preferably 250 g or less, relative to 1 L of the complexing agent. When the content of the solid electrolyte raw material is within the above range, the solid electrolyte raw material is easily mixed, the dispersion state of the raw materials is improved, and the reaction between the raw materials is promoted, so that the electrolyte precursor and further the solid electrolyte are easily obtained efficiently.
[0077] There is no particular limitation on the method of mixing the solid electrolyte raw material and the complexing agent, and the raw material contained in the solid electrolyte raw material and the complexing agent may be added to a device capable of mixing the solid electrolyte raw material and the complexing agent and mixed. For example, it is preferable to supply the complexing agent into a tank, operate the stirring blade, and then gradually add the raw material, since this provides a good mixed state of the solid electrolyte raw material and improves the dispersibility of the raw material. In addition, when a halogen element is used as a raw material, the raw material may not be solid, specifically, fluorine and chlorine are gaseous, and bromine is liquid, at room temperature and pressure. For example, when the raw material is liquid, it may be supplied into the tank together with a complexing agent separately from other solid raw materials, and when the raw material is gas, it may be supplied by blowing into the mixture of the solid raw material and the complexing agent.
[0078] The method for producing a solid electrolyte according to the present embodiment is characterized by including mixing a solid electrolyte raw material with a complexing agent, and can be produced by a method that does not use equipment generally called a pulverizer, such as a media-type pulverizer such as a ball mill or a bead mill, which is used for the purpose of pulverizing a solid raw material. In the method for producing a solid electrolyte according to the present embodiment, the raw material and the complexing agent contained in the inclusion are mixed by simply mixing the solid electrolyte raw material with the complexing agent, and an electrolyte precursor can be formed. In addition, the mixture of the solid electrolyte raw material and the complexing agent may be pulverized by a pulverizer, since the mixing time for obtaining the electrolyte precursor can be shortened or the mixture can be finely pulverized.
[0079] An example of an apparatus for mixing the solid electrolyte raw material and the complexing agent is a mechanical stirring mixer equipped with stirring blades in a tank. Examples of mechanical stirring mixers include high-speed stirring mixers and double-arm mixers, and the high-speed stirring mixer is preferably used from the viewpoint of increasing the uniformity of the raw materials in the mixture of the solid electrolyte raw material and the complexing agent and obtaining higher ion conductivity. Examples of the high-speed stirring mixer include a vertical shaft rotary mixer and a horizontal shaft rotary mixer, and either type of mixer may be used.
[0080] Examples of the shape of the stirring blade used in the mechanical stirring mixer include a blade type, an arm type, a ribbon type, a multi-stage blade type, a double arm type, a shovel type, a biaxial blade type, a flat blade type, a C-shaped blade type, and the like. From the viewpoint of increasing the uniformity of the raw material in the solid electrolyte raw material and obtaining higher ion conductivity, the shovel type, the flat blade type, the C-shaped blade type, and the like are preferred.
[0081] The temperature conditions when mixing the solid electrolyte raw material and the complexing agent are not particularly limited, and are, for example, −30 to 100° C., preferably −10 to 50° C., and more preferably about room temperature (23° C.) (for example, about room temperature ±5° C.) The mixing time is about 0.1 to 150 hours, and from the viewpoint of more uniform mixing and obtaining higher ionic conductivity, is preferably 1 to 120 hours, more preferably 4 to 100 hours, and even more preferably 8 to 80 hours.
[0082] By mixing the solid electrolyte raw material with the complexing agent, an electrolyte precursor is obtained in which the lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms contained in the raw material are directly bonded to each other with and / or without the complexing agent due to the action of the complexing agent and the lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms contained in the raw material. That is, in the method for producing a solid electrolyte of this embodiment, the electrolyte precursor obtained by mixing the solid electrolyte raw material with the complexing agent is composed of the complexing agent, lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, and by mixing the solid electrolyte raw material with the complexing agent, a material containing the electrolyte precursor (hereinafter, sometimes referred to as "electrolyte precursor-containing material") is obtained. In this embodiment, the obtained electrolyte precursor is not completely dissolved in the complexing agent, which is a liquid, and a suspension containing the electrolyte precursor, which is a solid, is usually obtained. Therefore, the method for producing a solid electrolyte of this embodiment corresponds to a heterogeneous system in the so-called liquid phase method.
[0083] (Dry) The method for producing a solid electrolyte according to the present embodiment may include drying the electrolyte precursor-containing material (usually a suspension). This allows the electrolyte precursor powder to be obtained. By drying in advance, it becomes possible to efficiently perform heating. The drying and the subsequent heating may be performed in the same step.
[0084] Drying can be performed at a temperature according to the type of the remaining complexing agent (complexing agent not incorporated in the electrolyte precursor). For example, drying can be performed at a temperature equal to or higher than the boiling point of the complexing agent. Also, drying can be performed by drying under reduced pressure (vacuum drying) using a vacuum pump or the like at a temperature of usually 5 to 100°C, preferably 10 to 85°C, more preferably 15 to 70°C, and even more preferably about room temperature (23°C) (for example, about room temperature ±5°C) to volatilize the complexing agent.
[0085] The drying may be performed by filtering the electrolyte precursor-containing material using a glass filter or the like, by solid-liquid separation using decantation, or by solid-liquid separation using a centrifuge, etc. In this embodiment, after the solid-liquid separation, drying may be performed under the above-mentioned temperature conditions. Specifically, the solid-liquid separation can be easily carried out by transferring the electrolyte precursor-containing material to a container, and then removing the complexing agent and solvent that form a supernatant after the electrolyte precursor has precipitated, or by filtration using a glass filter having a pore size of about 10 to 200 μm, preferably 20 to 150 μm.
[0086] The electrolyte precursor is composed of a complexing agent, a lithium atom, a sulfur atom, a phosphorus atom, and a halogen atom. In addition, depending on the drying temperature, a peak different from the peak derived from the raw material may be observed in the X-ray diffraction pattern in the X-ray diffraction measurement. In this embodiment, the electrolyte precursor preferably contains a cocrystal composed of a complexing agent, a lithium atom, a sulfur atom, a phosphorus atom, and a halogen atom. In addition, the electrolyte precursor (cocrystal) is characterized by having a structure different from that of a solid electrolyte.
[0087] The cocrystal is composed of a complexing agent, a lithium atom, a sulfur atom, a phosphorus atom, and a halogen atom, and is typically presumed to form a complex structure in which the lithium atom is directly bonded to other atoms with and / or without the intervention of a complexing agent. Here, the fact that the complexing agent forms a co-crystal can be confirmed by, for example, gas chromatography analysis. Specifically, the powder of the electrolyte precursor is dissolved in methanol, and the resulting methanol solution is analyzed by gas chromatography to quantitatively determine the amount of the complexing agent contained in the co-crystal.
[0088] In the method for producing a solid electrolyte according to the present embodiment, it is preferable to form a co-crystal containing halogen atoms in terms of improving ionic conductivity. By using a complexing agent, a lithium-containing structure such as a PS4 structure and a lithium-containing raw material such as lithium halide are bonded (coordinated) via the complexing agent, and it becomes easier to obtain a co-crystal in which halogen atoms are more dispersed and fixed, thereby improving ionic conductivity.
[0089] The fact that the halogen atoms in the electrolyte precursor form a co-crystal can be confirmed by checking that a predetermined amount of halogen atoms is contained in the electrolyte precursor even after solid-liquid separation of the electrolyte precursor-containing material. This is because halogen atoms that do not form a co-crystal are more easily dissolved than halogen atoms that form a co-crystal and are discharged into the liquid of solid-liquid separation. It can also be confirmed by checking that the proportion of halogen atoms in the electrolyte precursor or solid electrolyte is not significantly reduced compared to the proportion of halogen atoms supplied from the raw material by composition analysis using ICP analysis (inductively coupled plasma atomic emission spectroscopy) of the electrolyte precursor or solid electrolyte. The amount of halogen atoms remaining in the electrolyte precursor is preferably 30% by mass or more, more preferably 35% by mass or more, and even more preferably 40% by mass or more, based on the charged composition. The upper limit of the amount of halogen atoms remaining in the electrolyte precursor is 100% by mass.
[0090] (heating) The method for producing a solid electrolyte of the present embodiment preferably includes heating an electrolyte precursor to obtain an amorphous solid electrolyte, and heating the electrolyte precursor or the amorphous solid electrolyte to obtain a crystalline solid electrolyte. By including heating the electrolyte precursor, the complexing agent in the electrolyte precursor is removed, and an amorphous solid electrolyte or a crystalline solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms is obtained. Here, the removal of the complexing agent in the electrolyte precursor is supported by the fact that the complexing agent constitutes a cocrystal of the electrolyte precursor from the results of X-ray diffraction patterns, gas chromatography analysis, etc., and that the solid electrolyte obtained by removing the complexing agent by heating the electrolyte precursor has the same X-ray diffraction pattern as the solid electrolyte obtained by the conventional method without using the complexing agent.
[0091] In the manufacturing method of the present embodiment, the solid electrolyte is obtained by removing the complexing agent in the electrolyte precursor by heating the electrolyte precursor, and the less the complexing agent in the solid electrolyte, the better, but the complexing agent may be contained to an extent that does not impair the performance of the solid electrolyte. The content of the complexing agent in the solid electrolyte is usually 10 mass % or less, preferably 5 mass % or less, more preferably 3 mass % or less, and further preferably 1 mass % or less.
[0092] In the manufacturing method of the present embodiment, the crystalline solid electrolyte may be obtained by heating an electrolyte precursor, or the electrolyte precursor may be heated to obtain an amorphous solid electrolyte, and the amorphous solid electrolyte may then be heated. That is, the manufacturing method of the present embodiment can also produce an amorphous solid electrolyte.
[0093] In the method for producing a solid electrolyte according to the present embodiment, whether to obtain an amorphous solid electrolyte, a crystalline solid electrolyte, or further to obtain a crystalline solid electrolyte after obtaining an amorphous solid electrolyte, or to obtain a crystalline solid electrolyte directly from an electrolyte precursor is appropriately selected as desired, and can be adjusted by the heating temperature, heating time, etc. The heating temperature of the electrolyte precursor may be determined according to the structure of the crystalline solid electrolyte obtained by heating the amorphous solid electrolyte (or electrolyte precursor), for example, when obtaining an amorphous solid electrolyte. Specifically, the amorphous solid electrolyte (or electrolyte precursor) is subjected to differential thermal analysis (DTA) at a temperature rise rate of 10°C / min using a differential thermal analyzer (DTA device), and the heating temperature is preferably set to 5°C or less, more preferably 10°C or less, and even more preferably 20°C or less, starting from the temperature of the top of the exothermic peak observed on the lowest temperature side. There is no particular limit to the lower limit, but it may be set to about -40°C or more, which is the temperature of the top of the exothermic peak observed on the lowest temperature side. By setting the temperature range, an amorphous solid electrolyte can be obtained more efficiently and reliably. The heating temperature for obtaining an amorphous solid electrolyte cannot be generally defined because it varies depending on the structure of the crystalline solid electrolyte to be obtained. Generally, however, it is preferably 135° C. or lower, more preferably 130° C. or lower, and even more preferably 125° C. or lower. There is no particular lower limit, but it is preferably 50° C. or higher, more preferably 70° C. or higher, even more preferably 80° C. or higher, still more preferably 100° C. or higher, and particularly preferably 110° C. or higher.
[0094] In addition, when the crystalline solid electrolyte is obtained by heating the amorphous solid electrolyte or directly from the electrolyte precursor, the heating temperature may be determined according to the structure of the crystalline solid electrolyte, and is preferably higher than the heating temperature for obtaining the amorphous solid electrolyte. Specifically, the amorphous solid electrolyte (or electrolyte precursor) is subjected to differential thermal analysis (DTA) at a temperature rise rate of 10°C / min using a differential thermal analyzer (DTA device), and the temperature is preferably set to 5°C or higher, more preferably 10°C or higher, and even more preferably 20°C or higher, starting from the peak top temperature of the exothermic peak observed on the lowest temperature side. There is no particular limit to the upper limit, but it may be about 40°C or lower. By setting the temperature range, the crystalline solid electrolyte can be obtained more efficiently and reliably. The heating temperature for obtaining a crystalline solid electrolyte cannot be generally defined because it varies depending on the structure of the crystalline solid electrolyte to be obtained. Generally, however, the heating temperature is preferably 130° C. or higher, more preferably 135° C. or higher, and even more preferably 140° C. or higher. There is no particular upper limit, but the heating temperature is preferably 300° C. or lower, more preferably 280° C. or lower, and even more preferably 250° C. or lower.
[0095] The heating time is not particularly limited as long as the desired amorphous solid electrolyte or crystalline solid electrolyte can be obtained, but is preferably, for example, 1 minute or more, more preferably 10 minutes or more, even more preferably 30 minutes or more, and even more preferably 1 hour or more. The upper limit of the heating time is not particularly limited, but is preferably 24 hours or less, more preferably 10 hours or less, even more preferably 5 hours or less, and even more preferably 3 hours or less.
[0096] Moreover, the heating is preferably carried out in an inert gas atmosphere (e.g., nitrogen atmosphere, argon atmosphere) or reduced pressure atmosphere (particularly in vacuum). This is because deterioration (e.g., oxidation) of the crystalline solid electrolyte can be prevented. The heating method is not particularly limited, and examples thereof include a method using a hot plate, a vacuum heating device, an argon gas atmosphere furnace, and a baking furnace. Furthermore, industrially, a horizontal dryer having a heating means and a feeding mechanism, a horizontal vibration fluidized dryer, etc. can also be used, and may be selected according to the amount of processing to be heated.
[0097] (Amorphous solid electrolyte) The amorphous solid electrolyte obtained by the method for producing a solid electrolyte of this embodiment contains lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms. Representative examples include solid electrolytes composed of lithium sulfide, phosphorus sulfide, and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, and Li2S-P2S5-LiI-LiBr; and solid electrolytes further containing other atoms such as oxygen atoms and silicon atoms, such as Li2S-P2S5-Li2O-LiI and Li2S-SiS2-P2S5-LiI. From the viewpoint of obtaining higher ionic conductivity, solid electrolytes composed of lithium sulfide, phosphorus sulfide, and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, and Li2S-P2S5-LiI-LiBr, are preferred. The types of atoms constituting the amorphous solid electrolyte can be confirmed, for example, by an ICP emission spectroscopic analyzer.
[0098] When the amorphous solid electrolyte obtained by the method for producing a solid electrolyte of this embodiment contains at least Li2S-P2S5, the molar ratio of Li2S to P2S5 is preferably 65-85:15-35, more preferably 70-80:20-30, and even more preferably 72-78:22-28, from the viewpoint of obtaining higher ionic conductivity. In the case where the amorphous solid electrolyte obtained by the method for producing a solid electrolyte of this embodiment is, for example, Li2S-P2S5-LiI-LiBr, the total content of lithium sulfide and diphosphorus pentasulfide is preferably 60 to 95 mol%, more preferably 65 to 90 mol%, and even more preferably 70 to 85 mol%. The ratio of lithium bromide to the total of lithium bromide and lithium iodide is preferably 1 to 99 mol%, more preferably 20 to 90 mol%, even more preferably 40 to 80 mol%, and particularly preferably 50 to 70 mol%.
[0099] In the amorphous solid electrolyte obtained by the method for producing a solid electrolyte of the present embodiment, the compounding ratio (molar ratio) of lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms is preferably 1.0-1.8:1.0-2.0:0.1-0.8:0.01-0.6, more preferably 1.1-1.7:1.2-1.8:0.2-0.6:0.05-0.5, and still more preferably 1.2-1.6:1.3-1.7:0.25-0.5:0.08-0.4. Furthermore, when bromine and iodine are used in combination as halogen atoms, the compounding ratio (molar ratio) of lithium atoms, sulfur atoms, phosphorus atoms, bromine, and iodine is preferably 1.0-1.8:1.0-2.0:0.1-0.8:0.01-0.3:0.01-0.3, more preferably 1.1-1.7:1.2-1.8:0.2-0.6:0.02-0.25:0.02-0.25, more preferably 1.2-1.6:1.3-1.7:0.25-0.5:0.03-0.2:0.03-0.2, and even more preferably 1.35-1.45:1.4-1.7:0.3-0.45:0.04-0.18:0.04-0.18. By setting the compounding ratio (molar ratio) of lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms within the above range, it becomes easier to obtain a solid electrolyte having a thiolithiregion II type crystal structure described below and having higher ion conductivity.
[0100] The shape of the amorphous solid electrolyte is not particularly limited, but may be, for example, particulate. The average particle diameter (D 50 ) can be, for example, in the range of 0.01 μm to 500 μm, or 0.1 to 200 μm.
[0101] (crystalline solid electrolyte) The crystalline solid electrolyte obtained by the method for producing a solid electrolyte according to the present embodiment may be a so-called glass ceramic obtained by heating an amorphous solid electrolyte to a crystallization temperature or higher. Examples of the crystal structure include a Li3PS4 crystal structure, a Li4P2S6 crystal structure, a Li7PS6 crystal structure, a Li7P3S 11 Examples of such structures include a crystal structure having peaks at 2θ=approximately 20.2° and 23.6° (for example, JP 2013-16423 A).
[0102] Also, Li 4-x Ge 1-x P x S4 thio-LISICON Region II crystal structure (Kanno et al., Journal of The Electrochemical Society, 148(7)A742-746(2001)), Li 4-x Ge 1-x P x PS4 such as S4-type thio-LISICON Region II type (see Solid State Ionics, 177 (2006), 2721-2725) 3- Also included are crystal structures which may have a framework. The crystalline solid electrolyte obtained by the method for producing a solid electrolyte of the present embodiment is particularly advantageous over the above-mentioned PS4 in that it has a higher ionic conductivity. 3- A solid electrolyte containing a Li skeleton is preferred, and a solid electrolyte containing a thiolicon region II type crystal structure is more preferred. Here, the "thiolicon region II type crystal structure" refers to a Li 4-x Ge 1-x P x S4 thio-LISICON Region II crystal structure, Li 4-x Ge 1-x P xIt indicates that the crystalline structure is either similar to the S4-based thio-LISICON Region II type. The crystalline solid electrolyte obtained by the manufacturing method of this embodiment may have the above-mentioned thio-LISICON Region II type crystal structure or may have it as the main crystal, but from the viewpoint of obtaining higher ionic conductivity, it is preferable that it has it as the main crystal. In this specification, "having it as the main crystal" means that the ratio of the target crystal structure among the crystal structures is 80% or more, preferably 90% or more, and more preferably 95% or more. In addition, it is preferable that the crystalline solid electrolyte obtained by the manufacturing method of this embodiment does not contain crystalline Li3PS4 (β-Li3PS4) from the viewpoint of obtaining higher ionic conductivity.
[0103] In X-ray diffraction measurements using CuKα radiation, the diffraction peaks of the Li3PS4 crystal structure appear, for example, at 2θ = 17.5°, 18.3°, 26.1°, 27.3°, and 30.0°, the diffraction peaks of the Li4P2S6 crystal structure appear, for example, at 2θ = 16.9°, 27.1°, and 32.5°, the diffraction peaks of the Li7PS6 crystal structure appear, for example, at 2θ = 15.3°, 25.2°, 29.6°, and 31.0°, and the diffraction peaks of the Li7P3S 11 Diffraction peaks of the crystal structure appear, for example, at 2θ = 17.8°, 18.5°, 19.7°, 21.8°, 23.7°, 25.9°, 29.6°, and 30.0°. 4-x Ge 1-x P x The diffraction peaks of the S4 thio-LISICON Region II crystal structure appear, for example, at 2θ = 20.1°, 23.9°, and 29.5°, and Li 4-x Ge 1-x P x Diffraction peaks of a crystal structure similar to the S4 thio-LISICON Region II type appear, for example, at 2θ=20.2 and 23.6°. Note that these peak positions may vary within a range of ±0.5°.
[0104] As described above, in this embodiment, when thiolicon region II type crystal structure is obtained, it is preferable that it does not contain crystalline Li3PS4 (β-Li3PS4).In this case, it is preferable that the solid electrolyte containing thiolicon region II type crystal structure does not have diffraction peaks at 2θ=17.5° and 26.1°.
[0105] The shape of the crystalline solid electrolyte is not particularly limited, but may be, for example, particulate. The average particle diameter (D 50 ) can be, for example, in the range of 0.01 μm to 500 μm, or 0.1 to 200 μm.
[0106] Next, regarding the above-mentioned embodiment B, this embodiment is an embodiment in which a raw material containing a solid electrolyte having a Li3PS4 structure or the like and a complexing agent, preferably the above-mentioned specific complexing agent, are used as the raw material in the manufacturing method of this embodiment, which is characterized by including mixing a solid electrolyte raw material containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms with a complexing agent. In the above-mentioned embodiment A, since the electrolyte precursor is formed while synthesizing the lithium-containing structure such as Li3PS4 present as the main structure in the solid electrolyte obtained by the manufacturing method of this embodiment by the reaction between raw materials such as lithium sulfide, it is considered that the composition ratio of the above-mentioned structure is likely to be small. Therefore, in embodiment B, a solid electrolyte containing the above structure is prepared by manufacturing or the like in advance, and is used as a raw material. As a result, the above structure and a raw material containing lithium, such as lithium halide, are bonded (coordinated) through a complexing agent, preferably the above specific complexing agent, and an electrolyte precursor in which halogen atoms are dispersed and fixed is more easily obtained. As a result, a solid electrolyte having high ion conductivity and suppressed generation of hydrogen sulfide is obtained.
[0107] Examples of raw materials containing lithium atoms, sulfur atoms, and phosphorus atoms that can be used in embodiment B include amorphous solid electrolytes having a Li3PS4 structure as a molecular structure (also referred to as "amorphous Li3PS4"), or crystalline solid electrolytes (also referred to as "crystalline Li3PS4"). From the viewpoint of suppressing hydrogen sulfide generation, amorphous solid electrolytes not containing a Li4P2S7 structure or crystalline solid electrolytes are preferred. These solid electrolytes can be produced by conventional production methods such as mechanical milling, slurry, and melt quenching, and commercially available products can also be used. In this case, the solid electrolyte containing lithium atoms, sulfur atoms, and phosphorus atoms is preferably an amorphous solid electrolyte, which improves the dispersibility of halogen atoms in the electrolyte precursor, and facilitates bonding between the halogen atoms and the lithium atoms, sulfur atoms, and phosphorus atoms in the solid electrolyte, resulting in a solid electrolyte having higher ion conductivity.
[0108] In embodiment B, the content of the amorphous solid electrolyte having a Li3PS4 structure, etc., relative to the total amount of the raw materials is preferably 60 to 100 mol %, more preferably 65 to 90 mol %, and even more preferably 70 to 80 mol %.
[0109] When an amorphous solid electrolyte having a Li3PS4 structure and a halogen element are used, the content of the halogen element relative to the amorphous solid electrolyte having a Li3PS4 structure is preferably 1 to 50 mol%, more preferably 2 to 40 mol%, even more preferably 3 to 25 mol%, and even more preferably 3 to 15 mol%.
[0110] Other than that, the case where a halogen element and a lithium halide are used, and the case where two kinds of halogen elements are used are the same as those in embodiment A.
[0111] In addition, in embodiment B, other than the above-mentioned raw materials, for example, the complexing agent, mixing, heating, drying, amorphous solid electrolyte, crystalline solid electrolyte, etc. are the same as those described in embodiment A above.
[0112] Next, regarding the above-mentioned embodiments C and D, these embodiments are different from each other in that a solvent is added to the solid electrolyte raw material and the complexing agent, preferably the above-mentioned specific complexing agent, in the above-mentioned embodiments A and B, as shown in the flow diagram of FIG. 2. The embodiments C and D are heterogeneous methods in which solid and liquid coexist, and in the embodiments A and B, a solid electrolyte precursor is formed in a liquid complexing agent. At this time, if the electrolyte precursor is easily dissolved in the complexing agent, separation of the components may occur. In the embodiments C and D, the elution of the components in the electrolyte precursor can be suppressed by using a solvent in which the electrolyte precursor is not dissolved.
[0113] (solvent) In this embodiment, it is preferable to add a solvent to the specific complexing agent. By mixing the solid electrolyte raw material and the complexing agent using a solvent, the effect of using the complexing agent is promoted, that is, the formation of the electrolyte precursor reacting with lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms is promoted, and it becomes easy to uniformly exist the structure containing lithium such as PS4 structure or the aggregate via the complexing agent, the raw material containing lithium such as lithium halide or the aggregate via the complexing agent, and the electrolyte precursor in which the halogen atoms are more dispersed and fixed is obtained, so that the effect of obtaining high ion conductivity is easily exhibited.
[0114] The method for producing a solid electrolyte according to the present embodiment is a so-called heterogeneous method, and it is preferable that the electrolyte precursor does not completely dissolve in the liquid complexing agent but precipitates. In the present embodiment, the solubility of the electrolyte precursor can be adjusted by adding a solvent. In particular, since halogen atoms are easily dissolved from the electrolyte precursor, the desired electrolyte precursor can be obtained by adding a solvent to suppress the dissolution of halogen atoms. As a result, a solid electrolyte having high ionic conductivity and suppressed generation of hydrogen sulfide can be obtained through an electrolyte precursor in which components such as halogen are dispersed.
[0115] More specifically, the solvent used in the present embodiment can be a wide variety of solvents that have been conventionally used in the production of solid electrolytes. Examples of the solvent include hydrocarbon solvents such as aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, and aromatic hydrocarbon solvents; solvents containing carbon atoms such as alcohol-based solvents, ester-based solvents, aldehyde-based solvents, ketone-based solvents, ether-based solvents, and solvents containing carbon atoms and heteroatoms; and the like. Any of these may be appropriately selected and used.
[0116] More specifically, examples of the solvent include aliphatic hydrocarbon solvents such as hexane, pentane, 2-ethylhexane, heptane, octane, decane, undecane, dodecane, and tridecane; alicyclic hydrocarbon solvents such as cyclohexane and methylcyclohexane; aromatic hydrocarbon solvents such as benzene, toluene, xylene, mesitylene, ethylbenzene, tert-butylbenzene, trifluoromethylbenzene, nitrobenzene, chlorobenzene, chlorotoluene, and bromobenzene; alcohol-based solvents such as ethanol and butanol; ester-based solvents such as ethyl acetate and butyl acetate; aldehyde-based solvents such as formaldehyde, acetaldehyde, and dimethylformamide, and ketone-based solvents such as acetone and methyl ethyl ketone; ether-based solvents such as diethyl ether, diisopropyl ether, dibutyl ether, tetrahydrofuran, dimethoxyethane, cyclopentyl methyl ether, tert-butyl methyl ether, and anisole; and solvents containing carbon atoms and hetero atoms such as acetonitrile, dimethyl sulfoxide, and carbon disulfide.
[0117] Among these solvents, aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, aromatic hydrocarbon solvents, and ether-based solvents are preferred, and from the viewpoint of obtaining more stable high ionic conductivity, heptane, cyclohexane, toluene, ethylbenzene, diethyl ether, diisopropyl ether, dibutyl ether, dimethoxyethane, cyclopentyl methyl ether, tert-butyl methyl ether, and anisole are more preferred, diethyl ether, diisopropyl ether, and dibutyl ether are even more preferred, diisopropyl ether and dibutyl ether are even more preferred, and dibutyl ether is particularly preferred. In the present embodiment, these solvents may be used alone or in combination of two or more kinds.
[0118] By using these solvents, compared to the above complexing agents i to iv, the solvent has a property of being relatively difficult to dissolve halogen atoms, raw materials containing halogen atoms such as lithium halide, and further components containing halogen atoms constituting the cocrystal contained in the electrolyte precursor (for example, an aggregate in which lithium halide and a complexing agent are bonded), etc., and the halogen atoms are easily fixed in the electrolyte precursor, and the halogen atoms are present in a well-dispersed state in the obtained electrolyte precursor and further in the solid electrolyte, making it easier to obtain a solid electrolyte having high ionic conductivity. That is, the solvent used in this embodiment preferably has a property of not dissolving the electrolyte precursor. The solvent used in this embodiment is preferably an organic solvent exemplified above, and is an organic solvent different from the above complexing agent. Note that some of these solvents overlap with those exemplified as other complexing agents other than the above complexing agents i to iv, and the overlapping ones may be considered to belong to either one, but considering the ease of dissolution, they may be treated as solvents. When a solvent is used, the content of the raw material in the solid electrolyte raw material may be determined based on 1 L of the total amount of the complexing agent and the solvent.
[0119] When a solvent is used in this embodiment, the electrolyte precursor-containing material can be dried at a temperature according to the type of the remaining complexing agent (complexing agent not incorporated in the electrolyte precursor) and the solvent. For example, the drying can be performed at a temperature equal to or higher than the boiling point of the complexing agent or the solvent. Also, the drying can be performed by volatilizing the complexing agent and the solvent by drying under reduced pressure (vacuum drying) using a vacuum pump or the like at usually 5 to 100°C, preferably 10 to 85°C, more preferably 15 to 70°C, and even more preferably at about room temperature (23°C) (for example, about room temperature ±5°C). Also, in the heating when a solvent is used in this embodiment, if the solvent remains in the electrolyte precursor, the solvent is also removed. However, unlike the complexing agent that constitutes the electrolyte precursor, the solvent is difficult to form the electrolyte precursor. Therefore, the amount of the solvent that can remain in the electrolyte precursor is usually 3 mass% or less, preferably 2 mass% or less, and more preferably 1 mass% or less.
[0120] In embodiment C, other than the above-mentioned solvent, for example, the complexing agent, mixing, heating, drying, amorphous solid electrolyte, crystalline solid electrolyte, etc. are the same as those described in embodiment A. Also, in embodiment D, other than the above-mentioned solvent, they are the same as embodiment B.
[0121] The solid electrolyte obtained by the method for producing a solid electrolyte of this embodiment has high ionic conductivity, excellent battery performance, and is less likely to generate hydrogen sulfide, so it is suitable for use in batteries. It is particularly suitable when lithium atoms are used as the conductive species. The solid electrolyte of this embodiment may be used in a positive electrode layer, a negative electrode layer, or an electrolyte layer. Each layer may be produced by a known method.
[0122] In addition, the battery preferably uses a current collector in addition to the positive electrode layer, electrolyte layer, and negative electrode layer, and a known current collector can be used. For example, a layer of a material that reacts with the solid electrolyte, such as Au, Pt, Al, Ti, or Cu, coated with Au or the like can be used.
[0123] [Electrolyte precursor] The electrolyte precursor of this embodiment is constituted by a complexing agent having a lithium atom, a sulfur atom, a phosphorus atom, a halogen atom, and an ester group, and having at least one branch. The electrolyte precursor of this embodiment is the same as the electrolyte precursor described in the above-mentioned method for producing a solid electrolyte. Also, the content of the complexing agent in the electrolyte precursor is preferably 10 mass% or more and 70 mass% or less, which is the same as the electrolyte precursor described in the above-mentioned method for producing a crystalline solid electrolyte. EXAMPLES
[0124] The present invention will now be described in detail with reference to examples, but the present invention is not limited to these examples in any way.
[0125] (Production Example 1) In a 1L reactor equipped with an impeller, 15.3 g of lithium sulfide and 24.7 g of diphosphorus pentasulfide were added under a nitrogen atmosphere. After the impeller was operated, 400 mL of tetrahydrofuran, which had been cooled to -20°C in advance, was introduced into the vessel. After allowing the temperature to rise naturally to room temperature (23°C), stirring was continued for 72 hours, and the resulting reaction liquid slurry was poured into a glass filter (pore size: 40-100 μm) to obtain a solid content, which was then dried at 90°C to obtain 38 g of Li3PS4 (purity: 90% by mass) as a white powder. The resulting powder was subjected to powder X-ray diffraction (XRD) measurement using an X-ray diffraction (XRD) device (SmartLab device, manufactured by Rigaku Corporation), which showed a halo pattern and confirmed that it was amorphous Li3PS4. It's not something like that.
[0126] Example 1 (Complexing Agent: N-Methylmorpholine, Embodiment A) In a Schlenk flask (volume: 100 mL) containing a stirring bar, 0.60 g (13 mmol) of lithium sulfide (Li2S), 0.97 g (4.4 mmol) of diphosphorus pentasulfide (P2S5), and 0.58 g (4.4 mmol) of lithium iodide (LiI) were introduced under a nitrogen atmosphere. The Schlenk flask was cooled in an ice bath, the stirring bar was rotated, and 20 mL of N-methylmorpholine, a complexing agent, was added. After stopping the cooling and allowing the reaction temperature to rise naturally to room temperature, stirring was continued for 72 hours. Excess N-methylmorpholine was removed from the obtained electrolyte precursor-containing material under vacuum (room temperature: 23°C) to obtain a powdered electrolyte precursor. The powdered electrolyte precursor was then heated under vacuum at 160°C for 2 hours to obtain a crystalline solid electrolyte (the heating temperature for obtaining a crystalline solid electrolyte (160°C in this example) is sometimes referred to as the "crystallization temperature"). The obtained electrolyte precursor and the crystalline solid electrolyte were subjected to powder X-ray diffraction (XRD) measurement using an X-ray diffraction (XRD) device ("D2 Phaser (product name)", manufactured by Bruker). The obtained X-ray analysis spectra are shown in Figures 3 and 4. In the X-ray diffraction spectrum of the electrolyte precursor (Fig. 3), many peaks different from those of the raw materials used and the obtained crystalline solid electrolyte were observed, and these were presumed to be peaks due to the complex with the complexing agent. In the X-ray diffraction spectrum of the crystalline solid electrolyte (Fig. 4), crystallization peaks were detected mainly at 2θ = 20.1°, 23.6°, and 29.3°, and it had a thiolicon region II type crystal structure. The ionic conductivity was measured and found to be 1.08 × 10 -3 (S / cm).
[0127] Example 2 (Complexing Agent: N-Methylmorpholine, Embodiment A) In a Schlenk flask (volume: 100 mL) containing a stirring bar, 0.60 g (13 mmol) of lithium sulfide (Li2S), 0.97 g (4.4 mmol) of diphosphorus pentasulfide (P2S5), 0.19 g (2.2 mmol) of lithium bromide (LiBr), and 0.29 g (2.2 mmol) of lithium iodide (LiI) were introduced under a nitrogen atmosphere. The Schlenk flask was cooled in an ice bath, the stirring bar was rotated, and 20 mL of the complexing agent N-methylmorpholine was added. After stopping the cooling and bringing the reaction temperature to room temperature, the stirring was continued for 72 hours. Excess complexing agent was distilled off from the obtained electrolyte precursor-containing material under vacuum (room temperature: 23°C) to obtain a powdered electrolyte precursor. The electrolyte precursor powder was then heated under vacuum at 180°C for 2 hours to obtain a crystalline solid electrolyte (the heating temperature for obtaining a crystalline solid electrolyte (180°C in this example) is sometimes referred to as the "crystallization temperature"). The obtained electrolyte precursor and the crystalline solid electrolyte were subjected to powder X-ray diffraction (XRD) measurement using an X-ray diffraction (XRD) device ("D2 Phaser (product name)", manufactured by Bruker). The obtained X-ray analysis spectra are shown in Figures 5 and 6. In the X-ray diffraction spectrum of the electrolyte precursor (Fig. 5), many peaks different from those of the raw materials used and the obtained crystalline solid electrolyte were observed, and these are presumed to be peaks due to the complex with the complexing agent. In the X-ray diffraction spectrum of the crystalline solid electrolyte (Fig. 6), crystallization peaks were detected mainly at 2θ = 20.3°, 23.6°, and 29.3°, and it had a thiolicon region II type crystal structure. The ionic conductivity was measured and found to be 1.27 × 10 -3 (S / cm).
[0128] Example 3 (N,N'-Dimethylpiperazine, embodiment A) In a Schlenk flask (volume: 50 mL) with a stirring bar, 1.70 g (Li3PS4: 1.53 g) of the white powder obtained in Production Example 1, 0.19 g of lithium bromide, and 0.28 g of lithium iodide were introduced under a nitrogen atmosphere. After rotating the stirring bar, 24 mL of the complexing agent N,N'-dimethylpiperazine was added, and stirring was continued for 24 hours. The obtained electrolyte precursor-containing material was dried under vacuum (room temperature: 23°C) to obtain a powdered electrolyte precursor. Next, the powdered electrolyte precursor was heated under vacuum at 140°C for 2 hours to obtain a crystalline solid electrolyte (the heating temperature (140°C in this example) for obtaining a crystalline solid electrolyte may be referred to as the "crystallization temperature"). The obtained electrolyte precursor and the crystalline solid electrolyte were subjected to powder X-ray diffraction (XRD) measurement using an X-ray diffraction (XRD) device ("D2 Phaser (product name)", manufactured by Bruker). The obtained X-ray analysis spectra are shown in Figures 7 and 8. In the X-ray diffraction spectrum of the electrolyte precursor (Figure 7), many peaks different from those of the raw materials used and the obtained crystalline solid electrolyte were observed, and it is assumed that these are peaks due to the complex with the complexing agent. In the X-ray diffraction spectrum of the crystalline solid electrolyte (Figure 8), crystallization peaks were detected mainly at 2θ = 20.3°, 23.6°, and 29.3°, and it has a thiolithiregion II type crystal structure. When the ionic conductivity was measured, it was 1.30 × 10 -3 (S / cm).
[0129] Example 4 (Complexing Agent: N-Methylmorpholine, embodiment C) In a Schlenk flask (volume: 100 mL) containing a stirring bar, 0.60 g (13 mmol) of lithium sulfide (Li2S), 0.97 g (4.4 mmol) of diphosphorus pentasulfide (P2S5), 0.19 g (2.2 mmol) of lithium bromide (LiBr), and 0.29 g (2.2 mmol) of lithium iodide (LiI) were introduced under a nitrogen atmosphere. The Schlenk flask was cooled in an ice bath, the stirring bar was rotated, and then 17.3 ml of tetrahydrofuran as a solvent and 3.4 mL of N-methylmorpholine as a complexing agent were added. After stopping the cooling and bringing the reaction temperature to room temperature, the stirring was continued for 72 hours. Excess complexing agent was distilled off under vacuum from the electrolyte precursor-containing material obtained (room temperature: 23°C) to obtain a powder electrolyte precursor. The electrolyte precursor powder was then heated under vacuum at 180°C for 2 hours to obtain a crystalline solid electrolyte (the heating temperature for obtaining a crystalline solid electrolyte (180°C in this example) is sometimes referred to as the "crystallization temperature"). The obtained electrolyte precursor and the crystalline solid electrolyte were subjected to powder X-ray diffraction (XRD) measurement using an X-ray diffraction (XRD) device ("D2 Phaser (product name)", manufactured by Bruker). The obtained X-ray analysis spectra are shown in Figures 23 and 24. In the X-ray diffraction spectrum of the electrolyte precursor (Figure 23), many peaks different from those of the raw materials used and the obtained crystalline solid electrolyte were observed, and it was assumed that these were peaks due to the complex with the complexing agent. In the X-ray diffraction spectrum of the crystalline solid electrolyte (Figure 24), crystallization peaks were detected mainly at 2θ = 20.3°, 23.6°, and 29.3°, and it had a thiolicon region II type crystal structure. The ionic conductivity was measured and found to be 1.90 × 10 -3 (S / cm).
[0130] Reference Example 1 (Complexing Agent: N,N-Dimethylaminoacetonitrile, Embodiment A) In a Schlenk flask (volume: 100 mL) containing a stirring bar, 0.60 g (13 mmol) of lithium sulfide (Li2S), 0.97 g (4.4 mmol) of diphosphorus pentasulfide (P2S5), and 0.58 g (4.4 mmol) of lithium iodide (LiI) were introduced under a nitrogen atmosphere. The Schlenk flask was cooled in an ice bath, the stirring bar was rotated, and 21 mL of the complexing agent N,N-dimethylaminoacetonitrile was added. After stopping the cooling and setting the reaction temperature to room temperature, stirring was continued for 72 hours. From the obtained electrolyte precursor-containing material, the excess complexing agent was distilled off under vacuum (room temperature: 23°C) to obtain a powdered electrolyte precursor. Next, the powdered electrolyte precursor was heated under vacuum at 140°C for 2 hours to obtain a crystalline solid electrolyte (the heating temperature for obtaining a crystalline solid electrolyte (140°C in this example) is sometimes referred to as the "crystallization temperature"). The obtained electrolyte precursor and the crystalline solid electrolyte were subjected to powder X-ray diffraction (XRD) measurement using an X-ray diffraction (XRD) device ("D2 Phaser (trade name)", manufactured by Bruker). The obtained X-ray analysis spectra are shown in Figures 9 and 10. In the X-ray diffraction spectrum of the electrolyte precursor (Figure 9), many peaks different from those of the raw materials used and the obtained crystalline solid electrolyte were observed, and these are presumed to be peaks due to the complex with the complexing agent. In the X-ray diffraction spectrum of the crystalline solid electrolyte (Figure 10), crystallization peaks were detected mainly at 2θ = 20.6°, 23.6°, and 29.3°, and it had a thiolicon region II type crystal structure. The ionic conductivity was measured and found to be 3.19 × 10 -4 (S / cm).
[0131] Reference Example 2 (Complexing Agent: N,N-Diethylaminoacetonitrile, Embodiment A) In a Schlenk flask (volume: 100 mL) containing a stirring bar, 0.60 g (13 mmol) of lithium sulfide (Li2S), 0.97 g (4.4 mmol) of diphosphorus pentasulfide (P2S5), and 0.58 g (4.4 mmol) of lithium iodide (LiI) were introduced under a nitrogen atmosphere. The Schlenk flask was cooled in an ice bath, the stirring bar was rotated, and 21 mL of the complexing agent N,N-diethylaminoacetonitrile was added. After stopping the cooling and bringing the reaction temperature to room temperature, stirring was continued for 72 hours. The obtained electrolyte precursor-containing material was heated at 80°C under vacuum, and the excess complexing agent was distilled off to obtain a powdered electrolyte precursor. The powdered electrolyte precursor was then heated at 140°C under vacuum for 2 hours to obtain a crystalline solid electrolyte (the heating temperature for obtaining a crystalline solid electrolyte (140°C in this example) may be referred to as the "crystallization temperature"). The obtained electrolyte precursor and the crystalline solid electrolyte were subjected to powder X-ray diffraction (XRD) measurement using an X-ray diffraction (XRD) device ("D2 Phaser (product name)", manufactured by Bruker). The obtained X-ray analysis spectra are shown in Figures 11 and 12. In the X-ray diffraction spectrum of the electrolyte precursor (Figure 11), no peaks thought to be due to a complex with the solvent were observed, and a halo pattern was observed. It is presumed that the interaction between the complexing agent and the solid electrolyte weakened due to the formation of the N,N-diethylamino structure, and the complex had already decomposed at 80°C. In the X-ray diffraction spectrum of the crystalline solid electrolyte (Figure 12), crystallization peaks were detected mainly at 2θ = 20.4°, 23.6°, and 29.3°, indicating that it has a thiolicon region II type crystal structure. The ionic conductivity was measured and found to be 2.59 x 10 -4 (S / cm).
[0132] Reference Example 3 (Complexing Agent: N,N-Dimethylaminopropionitrile, Embodiment A) In a Schlenk flask (volume: 100 mL) containing a stirring bar, 0.60 g (13 mmol) of lithium sulfide (Li2S), 0.97 g (4.4 mmol) of diphosphorus pentasulfide (P2S5), and 0.58 g (4.4 mmol) of lithium iodide (LiI) were introduced under a nitrogen atmosphere. The Schlenk flask was cooled in an ice bath, the stirring bar was rotated, and 21 mL of the complexing agent N,N-dimethylaminopropionitrile was added. After stopping the cooling and bringing the reaction temperature to room temperature, stirring was continued for 72 hours. The obtained electrolyte precursor-containing material was heated at 80°C under vacuum, and the excess complexing agent was distilled off to obtain a powdered electrolyte precursor. The powdered electrolyte precursor was then heated at 140°C under vacuum for 2 hours to obtain a crystalline solid electrolyte (the heating temperature for obtaining a crystalline solid electrolyte (140°C in this example) may be referred to as the "crystallization temperature"). The obtained electrolyte precursor and the crystalline solid electrolyte were subjected to powder X-ray diffraction (XRD) measurement using an X-ray diffraction (XRD) device ("D2 Phaser (product name)", manufactured by Bruker). The obtained X-ray analysis spectra are shown in Figures 13 and 14. In the X-ray diffraction spectrum of the electrolyte precursor (Figure 13), many peaks different from those of the raw materials used and the obtained crystalline solid electrolyte were observed, and it was assumed that these were peaks due to the complex with the complexing agent. In the X-ray diffraction spectrum of the crystalline solid electrolyte (Figure 14), crystallization peaks were detected mainly at 2θ = 20.3°, 23.6°, and 29.3°, and it had a thiolicon region II type crystal structure. The ionic conductivity was measured and found to be 3.40 × 10 -4 (S / cm).
[0133] Reference Example 4 (Complexing Agent: Diallyl Ether, Embodiment A) In a Schlenk flask (volume: 100 mL) containing a stirring bar, 0.60 g (13 mmol) of lithium sulfide (Li2S), 0.97 g (4.4 mmol) of diphosphorus pentasulfide (P2S5), 0.19 g (2.2 mmol) of lithium bromide (LiBr), and 0.29 g (2.2 mmol) of lithium iodide (LiI) were introduced under a nitrogen atmosphere. The Schlenk flask was cooled in an ice bath, the stirring bar was rotated, and then 23 mL of diallyl ether as a complexing agent was added. After stopping the cooling and setting the reaction temperature to room temperature, stirring was continued for 72 hours. From the obtained electrolyte precursor-containing material, the excess complexing agent was distilled off under vacuum (room temperature: 23°C) to obtain a powdered electrolyte precursor. Next, the powdered electrolyte precursor was heated under vacuum at 200°C for 2 hours to obtain a crystalline solid electrolyte (the heating temperature for obtaining a crystalline solid electrolyte (200°C in this example) is sometimes referred to as the "crystallization temperature"). The obtained electrolyte precursor and the crystalline solid electrolyte were subjected to powder X-ray diffraction (XRD) measurement using an X-ray diffraction (XRD) device ("D2 Phaser (product name)", manufactured by Bruker). The obtained X-ray analysis spectra are shown in Figures 15 and 16. In the X-ray diffraction spectrum of the electrolyte precursor (Figure 15), no peaks thought to be due to a complex with the solvent were observed, and a halo pattern was observed. When diallyl ether was used as a complexing agent, the interaction between the complexing agent and the solid electrolyte was not very strong, and it is presumed that the complex was decomposed by reducing the pressure at room temperature. In the X-ray diffraction spectrum of the crystalline solid electrolyte (Figure 16), crystallization peaks were detected mainly at 2θ = 20.6°, 23.6°, and 29.8°, and it had a thiolicon region II type crystal structure. The ionic conductivity was measured to be 5.35 × 10 -4 (S / cm).
[0134] Reference Example 5 (Complexing Agent: Diisopropylamine, Embodiment B) In a Schlenk flask (volume: 50 mL) containing a stirring bar, 1.70 g of the white powder obtained in Production Example 1 (Li3PS4: 1.53 g, 8.5 mmol), 0.19 g (2.2 mmol) of lithium bromide (LiBr), and 0.28 g (2.1 mmol) of lithium iodide (LiI) were introduced under a nitrogen atmosphere. The Schlenk flask was cooled in an ice bath, the stirring bar was rotated, and 20 mL of diisopropylamine as a complexing agent was added. After stopping the cooling and setting the reaction temperature to room temperature, stirring was continued for 72 hours. The obtained electrolyte precursor-containing material was heated at 80° C. under vacuum, and the excess complexing agent was distilled off to obtain a powdered electrolyte precursor. Next, the powdered electrolyte precursor was heated at 150° C. under vacuum for 2 hours to obtain a crystalline solid electrolyte (the heating temperature for obtaining a crystalline solid electrolyte (150° C. in this example) may be referred to as the "crystallization temperature"). The obtained electrolyte precursor and the crystalline solid electrolyte were subjected to powder X-ray diffraction (XRD) measurement using an X-ray diffraction (XRD) device ("D2 Phaser (product name)", manufactured by Bruker). The obtained X-ray analysis spectra are shown in Figures 17 and 18. In the X-ray diffraction spectrum of the electrolyte precursor (Figure 17), no peaks thought to be due to a complex with the solvent were observed, and a halo pattern was observed. It is believed that the addition of branching weakened the interaction between the solvent and electrolyte, and the complex had already decomposed at 80°C. In the X-ray diffraction spectrum of the crystalline solid electrolyte (Figure 18), crystallization peaks were detected mainly at 2θ = 20.3°, 23.8°, and 29.6°, indicating that it has a thiolithiregion II type crystal structure. The ionic conductivity was measured and found to be 1.03 x 10 -3 (S / cm).
[0135] (Reference Example 6) (Complexing agent: diisobutylamine, embodiment B) In a Schlenk flask (volume: 50 mL) containing a stirring bar, 1.70 g of the white powder obtained in Production Example 1 (Li3PS4: 1.53 g, 8.5 mmol), 0.19 g (2.2 mmol) of lithium bromide (LiBr), and 0.28 g (2.1 mmol) of lithium iodide (LiI) were introduced under a nitrogen atmosphere. The Schlenk flask was cooled in an ice bath, the stirring bar was rotated, and 20 mL of diisopropylamine as a complexing agent was added. After stopping the cooling and setting the reaction temperature to room temperature, stirring was continued for 72 hours. The obtained electrolyte precursor-containing material was heated at 80° C. under vacuum, and the excess complexing agent was distilled off to obtain a powdered electrolyte precursor. Next, the powdered electrolyte precursor was heated at 150° C. under vacuum for 2 hours to obtain a crystalline solid electrolyte (the heating temperature for obtaining a crystalline solid electrolyte (150° C. in this example) may be referred to as the "crystallization temperature"). The obtained electrolyte precursor and the crystalline solid electrolyte were subjected to powder X-ray diffraction (XRD) measurement using an X-ray diffraction (XRD) device ("D2 Phaser (product name)", manufactured by Bruker). The obtained X-ray analysis spectra are shown in Figures 19 and 20. In the X-ray diffraction spectrum of the electrolyte precursor (Figure 19), no peaks thought to be due to a complex with the solvent were observed, and a halo pattern was observed. It is believed that the addition of branching weakened the interaction between the solvent and electrolyte, and the complex had already decomposed at 80°C. In the X-ray diffraction spectrum of the crystalline solid electrolyte (Figure 20), crystallization peaks were detected mainly at 2θ = 20.3°, 23.8°, and 29.6°, indicating that it has a thiolicon region II type crystal structure.
[0136] Comparative Example 1 (Complexing Agent: Ethylene Glycol Monomethyl Ether Acetate, Embodiment B) An electrolyte precursor was prepared in the same manner as in Example 1, except that the complexing agent was changed to ethylene glycol monomethyl ether acetate. The electrolyte precursor was vacuum dried at 80°C for 2 hours, but it became syrup-like and the solvent could not be removed. The temperature was raised to 150°C, but it became syrup-like with high viscosity, so when it was returned to room temperature, it adhered to the flask in a syrup-like form. The syrup-like adhered matter was scraped off and crushed, and then powder X-ray diffraction (XRD) measurement was performed (Figure 21). In addition, when thermogravimetry was performed, a weight loss of about 30% by mass was confirmed, so a large amount of solvent remained, and it is considered that the interaction with the electrolyte precursor was strong and could not be removed because only compounds without a specific structure such as complexing agents i to iv were used.
[0137] Comparative Example 2 An electrolyte precursor was prepared in the same manner as in Example 1, except that the complexing agent in Example 1 was changed to dimethoxyethane, and the electrolyte precursor was heat-treated at 120° C. under vacuum to obtain a powder. In the X-ray diffraction spectrum of the powder ( FIG. 22 ), a strong peak derived from the raw material LiBr was observed. [Industrial Applicability]
[0138] According to the method for producing a solid electrolyte of the present embodiment, a solid electrolyte having high ionic conductivity can be produced by a liquid phase method. The solid electrolyte obtained by the method for producing the solid electrolyte of the present embodiment is suitable for use in batteries, particularly batteries used in information-related devices and communication devices such as personal computers, video cameras, and mobile phones.
Claims
1. A method for producing a solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, comprising mixing a complexing agent and a solid electrolyte raw material, wherein the complexing agent is a compound selected from the following complexing agents ii to iv. Complexing agent ii: a compound having an amino group and a nitrile group Complexing agent iii: a compound having an alkenyl group and an ether group Complexing agent iv: Compound having an amino group and a branched structure
2. A method for producing a solid electrolyte as described in claim 1, wherein the compound having an amino group and a nitrile group of the complexing agent ii is a non-alicyclic aliphatic compound.
3. A method for producing a solid electrolyte as described in claim 1 or 2, wherein the complexing agent ii, a compound having an amino group and a nitrile group, has a tertiary amino group.
4. A method for producing a solid electrolyte described in any one of claims 1 to 3, wherein the complexing agent ii, a compound having an amino group and a nitrile group, is at least one selected from N,N-dimethylaminoacetonitrile, N,N-diethylaminoacetonitrile and N,N-dimethylaminopropionitrile.
5. The method for producing a solid electrolyte according to claim 1, wherein the complexing agent iii, a compound having an alkenyl group and an ether group, has two or more alkenyl groups.
6. The method for producing a solid electrolyte according to claim 5, wherein the complexing agent iii, a compound having an alkenyl group and an ether group, has an unsaturated bond at its terminal.
7. The method for producing a solid electrolyte according to claim 5 or 6, wherein the complexing agent iii, a compound having an alkenyl group and an ether group, is an acyclic aliphatic compound.
8. The method for producing a solid electrolyte according to claim 5, wherein the complexing agent iii, a compound having an alkenyl group and an ether group, is diallyl ether.
9. The method for producing a solid electrolyte according to claim 1, wherein the complexing agent iv is a compound having an amino group and a branched structure, and the compound has a branched alkyl group selected from an isopropyl group and a tert-butyl group at an end thereof.
10. The method for producing a solid electrolyte according to claim 9, wherein the complexing agent iv is a compound having an amino group and a branched structure, and has a branched alkyl group selected from an isopropyl group and a tert-butyl group at both ends.
11. The method for producing a solid electrolyte according to claim 9 or 10, wherein the complexing agent iv is a compound having an amino group and a branched structure, and the compound is at least one selected from diisopropylamine and diisobutylamine.
Citation Information
Patent Citations
Liquid solution for formation of a solid electrolyte-containing layer of all-solid type lithium secondary battery, all-solid type lithium secondary battery, and method for manufacturing the same
JP2014191899A
Method of preparing sulfide-based solid electrolyte, and method of preparing all-solid secondary battery
JP2019200856A
Production method of solid electrolyte
WO2014192309A1
Solid electrolyte and method for producing solid electrolyte
WO2017159667A1
Solid lithium electrolytes and process of production
WO2018054709A1